Near-infrared fluorescent dye-loaded polymeric microparticles and their formulation for lesion labeling

JP2025506421AActive Publication Date: 2025-03-11NATIONAL CANCER CENTER(JP)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024546230
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-07-08
Filing Date
2023-01-27
Publication Date
2025-03-11
Estimated Expiration
2043-01-27

AI Technical Summary

Benefits of technology

【0052】 本発明による近赤外線蛍光染料搭載微粒子は、がんのような病変の位置に注入したときに、蛍光画像を通じて病変の位置をリアルタイムで正確に判別できるようにし、病変の切除のための手術の精度を画期的に高め、手術にかかる時間を大幅に短縮することができる。近赤外線蛍光染料とヒト血清アルブミン、または近赤外線蛍光染料とシクロデキストリンの複合体を形成し、これを微粒子内に搭載するか、または近赤外線蛍光染料をヒドロゲル高分子に混合して搭載することにより、近赤外線蛍光染料単独で微粒子を製造する場合に比べて微粒子で発生する蛍光の強度が強く、微粒子内での蛍光染料の安定性を向上させ、標識された部位を長期間蛍光画像で確認できるようになる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025506421000001_ABST
    Figure 2025506421000001_ABST
Patent Text Reader

Abstract

The present invention relates to microparticles loaded with near-infrared fluorescent dyes and their preparations, and more specifically, to microparticles loaded with near-infrared fluorescent dyes that can be injected into a lesion such as cancer to accurately identify the location of the lesion from a fluorescent image during surgery, thereby enabling precision surgery. The near-infrared fluorescent dye-loaded microparticles according to the present invention, when injected into a lesion such as cancer, can accurately determine the location of the lesion from a fluorescent image in real time, dramatically improving the accuracy of surgery for resecting the lesion and significantly shortening the time required for surgery. By forming a complex between a near-infrared fluorescent dye and human serum albumin or a near-infrared fluorescent dye and cyclodextrin and loading it into the microparticles, or by mixing the near-infrared fluorescent dye into a hydrogel polymer and loading it, the intensity of the fluorescence generated by the microparticles is stronger than when the microparticles are manufactured using only the near-infrared fluorescent dye, and the stability of the fluorescent dye in the microparticles is improved, making it possible to confirm the labeled site with a fluorescent image for a long period of time.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to microparticles loaded with near-infrared fluorescent dyes and preparations thereof, and more specifically, to microparticles loaded with near-infrared fluorescent dyes that, when injected into a lesion such as cancer, can accurately identify the location of the lesion from fluorescent images during surgery, enabling precision surgery. [Background technology]

[0002] Fluorescence imaging technology has the great advantage of being able to acquire images in real time while having high sensitivity compared to magnetic resonance imaging, nuclear medicine imaging, and ultrasound imaging, and is therefore evaluated as the most powerful tool for confirming and removing the location of lesions such as cancer in real time during surgery. Furthermore, as systems that can implement near-infrared fluorescence imaging functions in endoscopic and laparoscopic devices have been gradually commercialized in recent years, it is predicted that surgery using fluorescence images will be widely used in patient surgery in the future.

[0003] Laparoscopic surgery is a minimally invasive surgery that reduces the damage and impact on the patient's body. Instead of cutting open the abdomen or chest, a small hole of 0.5 to 1.5 cm is made and an endoscope (laparoscope) equipped with a special camera is inserted to view the inside of the abdominal cavity while performing surgery using surgical tools (forceps, electric scalpel, hemostatic suture instruments, etc.). Laparoscopic surgery has developed over the past few decades due to its advantages over open surgery, such as less postoperative pain, faster recovery time due to fewer incisions, and shorter hospital stays. In recent years, with the introduction of robotic surgery, which applies laparoscopic surgery, laparoscopic surgery has been accepted as the basis of surgical techniques. For surgical treatment of colon cancer, stomach cancer, etc., it is necessary to insert an endoscope into the stomach or colon and check the treatment site, for example the cancer site, with the naked eye before incising and removing the cancer site through laparoscopic surgery. However, in conventional surgical methods, the viewing angle and range obtained through an endoscope are completely different from the viewing angle and range obtained through a laparoscope, so it is difficult to accurately find the target location to be incised, and therefore the precision and range of incision can only vary depending on the skill of the surgeon, and the range of incision can only be large. Therefore, in order to mark the area to be removed in surgery, a method is used in which a drug such as Indian ink is injected into the lesion confirmed using an endoscope using an endoscopic injection needle to display the lesion area, and the surgery is performed while checking the area marked with Indian ink with the naked eye through the laparoscope during surgery. However, this marking method has the disadvantage that complications may occur due to ink being mistakenly injected into the muscle layer, and the ink or dye may bleed into the surrounding area at the injected area, causing the area to be removed in surgery to expand. Therefore, in order to minimize the area of ​​normal tissue removed during laparoscopic surgery, a contrast agent for "marking" or "marker" that indicates the appropriate location of the diseased lesion is required.

[0004] In recent years, attempts have been made to use near-infrared fluorescent dyes to mark lesions. Fluorescence imaging techniques using near-infrared fluorescent dyes have the advantage that not only can the marked sites located in deep tissues be detected from the fluorescent images, but also that the fluorescent signals can be detected sensitively even with a small amount of fluorescent dye. Fluorescence imaging techniques have the great advantage of being able to acquire images in real time while being highly sensitive compared to magnetic resonance imaging, nuclear medicine imaging, and ultrasound imaging, and are therefore evaluated as the most powerful tool for confirming the location of lesions such as cancer in real time during surgery and removing them. As a fluorescent imaging contrast agent that has been tried so far, indocyanine green, a near-infrared fluorescent dye approved for clinical use by the U.S. Food and Drug Administration (FDA), has been used for vascular imaging, etc., but there are various limitations to its clinical application. Indocyanine green reduces its fluorescent brightness due to the concentration-dependent aggregation phenomenon, and is chemically unstable in aqueous solution and easily decomposed. In addition, it has the disadvantage that it rapidly spreads or is absorbed from the injection site into the surrounding tissues, generating fluorescent signals over a wider area than the injection site and that the fluorescent signals become weak within a short time after injection. For this reason, there is a need to develop a method that can increase the labeling efficiency for lesions and maintain the fluorescent signal of the near-infrared fluorescent dye at a high level for a long time without bleeding at the labeled site.

[0005] Long Wang et al. fabricated microbubbles loaded with indocyanine green dye for detection of sentinel lymph nodes using ultrasound and fluorescence imaging. Microbubbles made of poly(D,L-lactide-co-glycolide) (PLGA), a biodegradable polymer, exhibited ultrasound imaging contrast effects, and by loading indocyanine green into the microbubbles, the location of the sentinel lymph node could be confirmed from ultrasound and near-infrared fluorescence images when the microbubbles migrated from the injection site and accumulated in the sentinel lymph node. However, as mentioned above, indocyanine green is unstable and tends to aggregate with each other in aqueous solutions. Therefore, when indocyanine green is used alone and loaded into microbubbles, the intensity of the fluorescent signal is greatly weakened due to the aggregation phenomenon between indocyanine green molecules, and the further decrease in the fluorescence intensity due to the decomposition of indocyanine green over time becomes a problem. In addition, in the case of microbubbles, if a hole is formed in the shell layer during the manufacturing process or due to hydrolysis in the body, the loaded indocyanine green may be rapidly released to the outside, resulting in a decrease in the fluorescent signal and bleeding of the fluorescent signal into the surrounding tissue.

[0006] The present invention has been devised to solve the problems of the prior art as described above, and has been accomplished by developing polymer microparticles loaded with a near-infrared fluorescent dye complex in which a near-infrared fluorescent dye and human serum albumin, or a near-infrared fluorescent dye and cyclodextrin form a complex. The near-infrared fluorescent dye-loaded microparticles allow the fluorescent dye loaded in the microparticles to remain in the microparticles for a long period of time while generating a strong fluorescent signal, thereby enabling the location of the lesion into which the microparticles are injected to be identified accurately and for a long period of time through fluorescent images.

[0007] When the location of a lesion is marked using the microparticles loaded with the near-infrared fluorescent dye developed in the present invention and their preparations, the marked location can be confirmed through fluorescent images, allowing for accurate resection of the lesion during surgery, and the time required for surgery can be significantly reduced. In addition, the near-infrared fluorescent dye loaded in the microparticles can be tracked through images for a long period of time, allowing the changes occurring at the marked location to be tracked for a long period of time. Summary of the Invention technical challenges

[0008] One exemplary object of the present invention is to provide a polymeric microparticle for labeling a lesion, the polymeric microparticle being loaded with a near-infrared fluorescent dye, the near-infrared fluorescent dye forming a complex with human serum albumin or cyclodextrin.

[0009] Another exemplary object of the present invention is to provide a method for producing said polymeric microparticles.

[0010] Yet another exemplary object of the present invention is to provide a composition for labeling a lesion, comprising said polymeric microparticles.

[0011] Yet another exemplary object of the present invention is to provide a method for labeling a lesion, comprising injecting said composition into an individual.

[0012] Yet another exemplary object of the present invention is to provide a use of said composition for marking of lesions.

[0013] The technical problem to be achieved by the technical ideas of the invention disclosed in this specification is not limited to the problem of solving the problems mentioned above, and other problems not mentioned will be clearly understood by those of ordinary skill in the art from the following description. [Means for solving the problem]

[0014] This will be specifically described as follows. Meanwhile, each description and embodiment disclosed in this application can be applied to each of the other descriptions and embodiments. In other words, all combinations of various elements disclosed in this application belong to the scope of this application. In addition, it cannot be said that the scope of this application is limited by the specific description described below.

[0015] As one aspect for achieving the above-mentioned object, the present invention provides polymer microparticles for labeling lesions, which are loaded with a near-infrared fluorescent dye for labeling lesions, and the near-infrared fluorescent dye forms a complex with human serum albumin or cyclodextrin.

[0016] The lesion marking method involves marking the location of the lesion to be removed by surgery beforehand, and then using fluorescent images during surgery to confirm the marked location in real time, thereby enabling accurate surgery and reducing the surgical time.

[0017] In the present invention, the near-infrared fluorescent dye is indocyanine green, IRDye 800CW carboxylate (IRDye 800CW), Alexa Fluor 647, Alexa Fluor 660, Alexa Fluor 680, Alexa Fluor 700, Alexa Fluor 750, Alexa Fluor 780, Flamma 749, Flamma 774, Flamma 800, FSD Fluor TM 647, FSD Fluor TM 680, FSD Fluor TM 750, FSD Fluor TM 800, sulfo-cyanine 5 carboxylic acid (Cy5), sulfo-cyanine 5.5 carboxylic acid (Cy5.5), sulfo-cyanine 7 carboxylic acid (Cy7), or sulfo-cyanine 7.5 carboxylic acid (Cy7.5), but is not limited to these.

[0018] The near infrared fluorescent dye may be a dye that produces a fluorescent signal at wavelengths of 650 nm or greater.

[0019] Indocyanine green has been used in vascular imaging as a fluorescent imaging contrast agent approved for clinical use by the U.S. Food and Drug Administration (FDA), but there are various limitations to its clinical application. Indocyanine green loses fluorescence brightness due to concentration-dependent aggregation, and is easily decomposed due to its chemical instability in aqueous solution. In addition, it has the disadvantage that it is rapidly diffused or absorbed by the surrounding tissues from the injection site, so that it generates a fluorescent signal over a wider area than the injection site, or the fluorescent signal becomes weak within a short time after injection. For this reason, there is a need to develop a method that can increase the labeling efficiency of lesions and maintain the fluorescent signal of the near-infrared fluorescent dye at a high level for a long time without bleeding at the labeled site.

[0020] Indocyanine green has a tendency to aggregate with itself in aqueous solution and is therefore unstable. Therefore, when indocyanine green is used alone, the intensity of the fluorescent signal is significantly weakened due to the aggregation phenomenon between indocyanine green molecules, and over time, the fluorescence intensity further decreases due to the decomposition of indocyanine green, which becomes a problem.

[0021] The microparticles according to the present invention, which are loaded with a complex of near-infrared fluorescent dye and human serum albumin, or a complex of near-infrared fluorescent dye and cyclodextrin, allow the fluorescent dye loaded in the microparticles to remain in the microparticles for a long period of time while emitting a strong fluorescent signal, thereby enabling the location of the target site to be accurately and long-term determined by fluorescent images.

[0022] In the present invention, a water-in-oil-in-water (W1 / O / W2) emulsion method can be used as a manufacturing method for loading the complex into polymeric microparticles. When a near-infrared fluorescent dye with low solubility in water is loaded into a microparticle alone, aggregation of the near-infrared fluorescent dye occurs within the microparticle, resulting in a very weak fluorescent signal generated from the prepared microparticle and a low chemical / physical stability of the near-infrared fluorescent dye within the microparticle. When a complex of a near-infrared fluorescent dye and human serum albumin, or a near-infrared fluorescent dye and cyclodextrin is formed and loaded into the microparticle, the aggregation phenomenon that occurs when a fluorescent dye is loaded alone can be prevented, the fluorescent signal generated in the microparticle is much stronger, and the chemical / physical stability of the fluorescent dye is also increased.

[0023] In the present invention, the polymer may be a biodegradable polymer, which may be, but is not limited to, poly(lactide-co-glycolide) (PLGA), poly(DL-lactide-co-glycolide) (PDLGA), poly(glycolic acid) (PGA), poly(lactide) (PLA), poly(hydroxybutyrate), polycaprolactone (PCL), polydioxanone (PDO), poly(amino acids), polyanhydrides, polyorthoesters, or polyphosphazenes.

[0024] In the present invention, the polymer can form a block copolymer with poly(ethylene oxide) (PEG).

[0025] As an example, the polymer may form a block copolymer with poly(D,L-lactide)-block-poly(ethylene glycol) (PDLLA-PEG).

[0026] In the present invention, the polymer may be a non-biodegradable polymer, poly(methyl methacrylate) (PMMA) or polycarbonate (PC).

[0027] In the present invention, the microparticles may further include alginic acid or hyaluronic acid together with the complex of near-infrared fluorescent dye and human serum albumin, or near-infrared fluorescent dye and cyclodextrin.When the complex is dispersed and loaded in alginic acid or hyaluronic acid hydrogel, the aggregation phenomenon of fluorescent dyes can be prevented more effectively than when the complex is loaded alone in the microparticles, the fluorescent signal generated by the microparticles becomes significantly stronger, and the chemical and physical stability of the fluorescent dye is also improved.

[0028] Additionally, mixing the near-infrared fluorescent dye present in the W1 phase; the near-infrared fluorescent dye and human serum albumin; or the near-infrared fluorescent dye and cyclodextrin with hydrogels using polymers such as alginate or hyaluronic acid can further slow down the release of the fluorescent dye from the microparticles.

[0029] In the present invention, the microparticles contain one or more cavities (isolated spaces) within the microparticles, and the complex of the near-infrared fluorescent dye and human serum albumin, or the complex of the near-infrared fluorescent dye and cyclodextrin, may be loaded into the cavities.

[0030] In particular, if multiple isolated spaces are created within the microparticles and near-infrared fluorescent dye is loaded into them, the fluorescent dye loaded in the isolated spaces within the microparticles will not be released early even if the outer shell of the microparticles decomposes to form holes. In this way, if multiple isolated spaces are created within the microparticles and fluorescent dye is loaded into them, the problem of unnecessary release of fluorescent dye that occurs in microbubbles can be solved.

[0031] In the present invention, the fine particles may further contain a surfactant.

[0032] The surfactant may be any one selected from polyvinyl alcohol, polyethylene glycol, Labrafil, Labrasol, medium chain triglyceride, lecithin, N-methyl pyrrolidone, polyvinyl pyrrolidone, hydropropyl methylcellulose, poloxamer (e.g., poloxamer 188 (P-188), poloxamer 407 (P-407)), or Tween (e.g., Tween-80, Tween-20)).

[0033] The microparticles of the present invention can be dispersed in an aqueous solution in which the surfactant or hydrophilic polymer is dissolved, for injection into the target site. The hydrophilic polymers include carboxymethylcellulose, gelatin, collagen, alginic acid, hyaluronic acid, etc.

[0034] When the microparticles are prepared in the form of a pellet together with a hydrogel polymer and injected into the site to be labeled using a syringe, the microparticles can be prevented from migrating from the injection site, and the release of the fluorescent dye into the surrounding tissue can be further suppressed. The hydrogel polymer can be a temperature-sensitive polymer such as poloxamer, or alginic acid or hyaluronic acid, or a derivative thereof, which causes an ionic crosslinking reaction.

[0035] In the present invention, the microparticles may be for coating on the surface of a metal or non-metal material.

[0036] The coating may be by adhesives or rubbers.

[0037] In one embodiment of the present invention, the microparticles can be coated onto the surface of metal and / or non-metallic materials together with adhesives or rubber agents to produce lesion markers using metal and / or non-metallic materials.

[0038] The adhesive may be, for example, but not limited to, urea-based, melamine-based, phenol-based, unsaturated polyester-based, epoxy-based, resorcinol-based, vinyl acetate-based, polyvinyl alcohol-based, vinyl chloride-based, polyvinyl acetal-based, acrylic-based, saturated polyester-based, polyamide-based, or polyethylene-based.

[0039] The rubber agent may be, for example, but not limited to, butadiene rubber, nitrile rubber, butyl rubber, silicone rubber, chloroprene rubber, latex-free rubber (NFR), neoprene, natural latex, or synthetic latex.

[0040] In another aspect for achieving the above object, the present invention provides a method for producing polymeric microparticles for labeling lesions, comprising the steps of forming a complex between a near-infrared fluorescent dye and human serum albumin, or between a near-infrared fluorescent dye and cyclodextrin; and loading the complex into a polymeric microparticle.

[0041] In the present invention, a water-in-oil-in-water (W1 / O / W2) emulsion method can be used as a method for loading the complex into polymeric microparticles.

[0042] In the present invention, the method may further include a step of mixing the near infrared fluorescent dye with a hydrogel polymer to load the dye into polymer particles.

[0043] In the present invention, in order to further increase the fluorescent signal of the near-infrared fluorescent dye loaded in the microparticles, the microparticles can be manufactured by mixing a polymer and a surfactant in an oil phase.

[0044] In still another embodiment to achieve the above object, the present invention provides a composition for labeling a lesion, comprising the above-mentioned polymeric microparticles.

[0045] The fluorescent dye, polymer, fine particles, and surfactant are as described above.

[0046] In the present invention, the microparticles may be mixed with methylcellulose, alginic acid, hyaluronic acid, polyvinyl alcohol, collagen, gelatin, Tween, Poloxamer, or polyvinylpyrrolidone.Specifically, the microparticles may be in a form dispersed in an aqueous solution in which methylcellulose, alginic acid, hyaluronic acid, polyvinyl alcohol, collagen, gelatin, Tween, Poloxamer, or polyvinylpyrrolidone is dissolved.

[0047] In the present invention, the composition for marking the lesion may be prepared so as to be injectable via a syringe.

[0048] In the present invention, the composition for labeling the lesion may be in the form of a liquid or a solid pellet, specifically in the form of a solid pellet.

[0049] In yet another aspect to achieve the above object, the present invention provides a method for labeling a lesion, comprising the step of injecting the above composition into an individual.

[0050] In one embodiment of the present invention, the individual may be, but is not limited to, a human, monkey, cow, horse, sheep, pig, chicken, turkey, quail, cat, dog, mouse, rat, rabbit, or guinea pig, and may be specifically a mammal, more specifically a human.

[0051] In yet another aspect of achieving the above object, the present invention provides a use of the above composition for labeling a lesion. Effect of the Invention

[0052] The near-infrared fluorescent dye-loaded microparticles according to the present invention, when injected into the location of a lesion such as cancer, allow the location of the lesion to be accurately identified in real time through a fluorescent image, dramatically improving the precision of surgery for resecting the lesion and significantly shortening the time required for surgery. By forming a complex between a near-infrared fluorescent dye and human serum albumin or a near-infrared fluorescent dye and cyclodextrin and loading it into the microparticles, or by mixing the near-infrared fluorescent dye with a hydrogel polymer and loading it, the intensity of the fluorescence generated by the microparticles is stronger than when microparticles are manufactured using only a near-infrared fluorescent dye, and the stability of the fluorescent dye in the microparticles is improved, making it possible to confirm the labeled site through a fluorescent image for a long period of time. [Brief description of the drawings]

[0053] [Figure 1] FIG. 1 shows the morphology of polymer microparticles loaded with a near-infrared fluorescent dye complex and the composition for formulation. [Diagram 2] Figure 2 shows the fluorescence spectrum obtained by dissolving the same concentration of indocyanine green (ICG) and indocyanine green-human serum albumin (ICG-HSA) complex in aqueous solution. It can be seen that when ICG forms a complex with HSA, it shows a higher fluorescence signal. [Diagram 3] FIG. 3 shows scanning electron micrographs of (a) ICG-PLGA (without P-188), (b) ICG-HSA-PLGA (without P-188), and (c) ICG-HSA-PLGA (0.1% P-188) microparticles. [Figure 4]Figure 4 shows the fluorescence spectrum for comparing the fluorescence signals of ICG-HSA solution and ICG-PLGA (without P-188), ICG-HSA-PLGA (without P-188), and ICG-HSA-PLGA (0.1% P-188) microparticle dispersions. All samples were adjusted to the equivalent concentration of 30 μM ICG. In the case of ICG-PLGA (without P-188) microparticle dispersion loaded with ICG alone, the fluorescence signal was 6.8 times lower than that of ICG-HSA, and it can be seen that microparticles that generate a higher fluorescence signal can be produced when the ICG-HSA complex is loaded. [Diagram 5] Figure 5 shows scanning electron micrographs of (a) the surface of an ICG-HSA-PLGA (P-188 0.5%) microparticle, (b) the cross-section of an ICG-HSA-PLGA (P-188 0.5%) microparticle, (c) the surface of an ICG-HSA-PLGA (P-188 1.0%) microparticle, and (d) the cross-section of an ICG-HSA-PLGA (P-188 1.0%) microparticle. [Figure 6] Figure 6 shows the fluorescence spectra for comparing the fluorescence signals of the ICG-HSA solution and the ICG-PLGA (no P-188), ICG-HSA-PLGA (0.5% P-188), and ICG-HSA-PLGA (1.0% P-188) microparticle dispersions. [Figure 7] Figure 7 shows fluorescence images (λex=780 / 20 nm, λem=845 / 40 nm) of (a) ICG-HSA, (b) ICG-HSA-PLGA (P-188 0.5%), and (c) ICG-HSA-PLGA (P-188 1.0%) microparticle dispersions. [Figure 8] Figure 8 shows the fluorescence images (λex=780 / 20 nm, λem=845 / 40 nm) taken over time of subcutaneous injection of (a) ICG-HSA, (b) ICG-HSA-PLGA (P-188 0.5%), and (c) ICG-HSA-PLGA (P-188 1.0%) microparticle dispersions into SKH-1 hairless mice. [Figure 9]Figure 9 shows the analysis of the ROI (Region of Interest) values ​​of the fluorescent signal at the injection site over time when ICG-HSA, ICG-HSA-PLGA (P-188 0.5%), and ICG-HSA-PLGA (P-188 1.0%) microparticle dispersions were subcutaneously injected into SKH-1 hairless mice. [Figure 10] FIG. 10 shows scanning electron micrographs of (a) the surface and (b) the cross section of ICG-HSA-Alginate-PLGA and PDLLA-PEG (P-188 0.1%) microparticles. [Figure 11] FIG. 11 shows the fluorescence spectra for comparing the fluorescence signals of ICG-HSA solution and ICG-PLGA (no P-188), ICG-HSA-Alginate-PLGA, and PDLLA-PEG (0.1% P-188) microparticle dispersions. [Figure 12] Figure 12 shows fluorescence images (λex=780 / 20 nm, λem=845 / 40 nm) of (a) ICG-HSA and (b) ICG-HSA-Alginate-PLGA, PDLLA-PEG (P-188 0.1%) microparticle dispersions. [Figure 13] Figure 13 shows (a) ICG-HSA and (b) ICG-HSA-Alginate-PLGA, PDLLA-PEG (P-188 0.1%) microparticle dispersions subcutaneously injected into SKH-1 hairless mice, and shows fluorescence images taken over time (λex=780 / 20 nm, λem=845 / 40 nm). [Figure 14] Figure 14 is a graph showing the analysis of the ROI (Region of Interest) values ​​of the fluorescent signal at the injection site over time when ICG-HSA, ICG-HSA-Alginate-PLGA, and PDLLA-PEG (P-188 0.1%) microparticle dispersions were subcutaneously injected into SKH-1 hairless mice. [Figure 15] FIG. 15 shows scanning electron micrographs of (a) the surface and (b) the cross section of an ICG-HSA-PMMA (P-188 1.0%) microparticle. [Figure 16]FIG. 16 shows fluorescence spectra for comparing the fluorescence signals of an ICG-HSA solution and a microparticle dispersion of ICG-PLGA (without P-188) and ICG-HSA-PMMA (1.0% P-188). [Figure 17] FIG. 17 shows fluorescence images (λex=780 / 20 nm, λem=845 / 40 nm) of (a) ICG-HSA and (b) ICG-HSA-PMMA (P-188 1.0%) microparticle dispersions. [Figure 18] Figure 18 shows (a) ICG-HSA and (b) ICG-HSA-PMMA (P-188 1.0%) microparticle dispersions subcutaneously injected into SKH-1 hairless mice, and shows fluorescence images taken over time (λex=780 / 20 nm, λem=845 / 40 nm). [Figure 19] FIG. 19 is a graph showing the analysis of the ROI (Region of Interest) values ​​of the fluorescent signal at the injection site over time when ICG-HSA and ICG-HSA-PMMA (P-188 1.0%) microparticle dispersions were subcutaneously injected into SKH-1 hairless mice. [Figure 20] FIG. 20 shows scanning electron micrographs of (a) ICG-Alginate-PLGA (no P-188) and (b) ICG-Alginate-PLGA (0.1% P-188) microparticles. [Figure 21] FIG. 21 shows fluorescence spectra for comparing the fluorescence signals of an ICG-HSA solution and ICG-PLGA (no P-188), ICG-Alginate-PLGA (no P-188), and ICG-Alginate-PLGA (1.0% P-188) microparticle dispersions. [Figure 22] Figure 22 shows scanning electron micrographs of (a) the surface of an ICG-HSA-Alginate-PLGA (P-188 0.1%) microparticle, (b) the surface of an ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticle, and (c) the cross-section of an ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticle. [Diagram 23]FIG. 23 shows the fluorescence spectra for comparing the fluorescence signals of ICG-HSA solution and ICG-PLGA (no P-188), ICG-HSA-Alginate-PLGA (0.1% P-188), and ICG-HSA-Alginate-PLGA (0.5% P-188) microparticle dispersions. [Figure 24] Figure 24 shows fluorescence images (λex=780 / 20 nm, λem=845 / 40 nm) of (a) ICG-HSA, (b) ICG-HSA-Alginate-PLGA (P-188 0.1%), and (c) ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticle dispersions. [Diagram 25] Figure 25 shows (a) ICG-HSA and (b) ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticle dispersions injected subcutaneously into SKH-1 hairless mice, and shows fluorescence images taken over time (λex=780 / 20 nm, λem=845 / 40 nm). [Figure 26] FIG. 26 is a graph showing the analysis of the ROI (Region of Interest) values ​​of the fluorescent signal at the injection site over time when ICG-HSA and ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticle dispersions were subcutaneously injected into SKH-1 hairless mice. [Figure 27] FIG. 27 shows scanning electron micrographs of (a) the surface of an ICG-HSA-Alginate-PLGA (Tween 0.5%) microparticle and (b) the cross-section of an ICG-HSA-Alginate-PLGA (Tween 0.5%) microparticle. [Figure 28] FIG. 28 shows fluorescence spectra for comparing the fluorescence signals of an ICG-HSA solution, ICG-PLGA (without P-188), and an ICG-HSA-Alginate-PLGA (Tween 0.5%) microparticle dispersion. [Figure 29] FIG. 29 shows fluorescence images (λex=780 / 20 nm, λem=845 / 40 nm) of (a) ICG-HSA and (b) ICG-HSA-Alginate-PLGA (Tween 0.5%) microparticle dispersions. [Diagram 30] Figure 30 shows (a) ICG-HSA and (b) ICG-HSA-Alginate-PLGA (Tween 0.5%) microparticle dispersions subcutaneously injected into SKH-1 hairless mice, and shows fluorescence images taken over time (λex=780 / 20 nm, λem=845 / 40 nm). [Diagram 31] FIG. 31 is a graph showing the analysis of the ROI (Region of Interest) values ​​of the fluorescent signal at the injection site over time when ICG-HSA and ICG-HSA-Alginate-PLGA (Tween 0.5%) microparticle dispersions were subcutaneously injected into SKH-1 hairless mice. [Diagram 32] FIG. 32 shows scanning electron micrographs of (a) the surface of ICG-mCD-Alginate-PLGA (P-188 0.1%) microparticles and (b) the cross-section of ICG-mCD-Alginate-PLGA (P-188 0.1%) microparticles. [Diagram 33] FIG. 33 shows fluorescence spectra for comparison of the fluorescence signals of (a) ICG solution and ICG-mCD, (b) ICG-HSA solution and ICG-PLGA (no P-188), and ICG-mCD-Alginate-PLGA (0.1% P-188) microparticle dispersion. [Diagram 34] FIG. 34 shows fluorescence images (λex=780 / 20 nm, λem=845 / 40 nm) of (a) ICG-HSA and (b) ICG-mCD-Alginate-PLGA (P-188 0.1%) microparticle dispersions. [Diagram 35] Figure 35 shows (a) ICG-HSA and (b) ICG-mCD-Alginate-PLGA (P-188 0.1%) microparticle dispersions injected subcutaneously into SKH-1 hairless mice, and shows fluorescence images taken over time (λex=780 / 20 nm, λem=845 / 40 nm). [Diagram 36]FIG. 36 is a graph showing the analysis of the ROI (Region of Interest) values ​​of the fluorescent signal at the injection site over time when ICG-HSA and ICG-mCD-Alginate-PLGA (P-188 0.5%) microparticle dispersions were subcutaneously injected into SKH-1 hairless mice. [Figure 37] FIG. 37 is a graph comparing the fluorescence signal intensity depending on the concentration of Cy7 and Cy7-HSA solutions (λex=730 nm, λem=780 nm (Cy7), λem=786 nm (Cy7-HSA)). [Figure 38] Figure 38 shows scanning electron microscope photographs of (a) the surface of a Cy7-PMMA (without P-188) microparticle, (b) the cross-section of a Cy7-PMMA (without P-188) microparticle, (c) the surface of a Cy7-HSA-PMMA (without P-188) microparticle, (d) the cross-section of a Cy7-HSA-PMMA (without P-188) microparticle, (e) the surface of a Cy7-HSA-PMMA (1.0% P-188) microparticle, and (f) the cross-section of a Cy7-HSA-PMMA (1.0% P-188) microparticle. [Figure 39] Figure 39 is a graph comparing the fluorescence spectra (λex = 730 nm) of a Cy7 aqueous solution, a Cy7-HSA aqueous solution, a Cy7-PMMA (without P-188) microparticle dispersion, a Cy7-HSA-PMMA (without P-188) microparticle dispersion, and a Cy7-HSA-PMMA (1.0% P-188) microparticle dispersion prepared at the same Cy7 concentration (30 μM). [Diagram 40] FIG. 40 is a graph comparing the fluorescence signal intensity depending on the concentration of Cy7.5 and Cy7.5-HSA solutions (λex=730 nm, λem=810 nm (Cy7.5), λem=824 nm (Cy7.5)-HSA). [Diagram 41]FIG. 41 shows scanning electron micrographs of (a) the surface of a Cy7.5-PMMA (without P-188) microparticle, (b) the cross-section of a Cy7.5-PMMA (without P-188) microparticle, (c) the surface of a Cy7.5-HSA-PMMA (without P-188) microparticle, (d) the cross-section of a Cy7.5-HSA-PMMA (without P-188) microparticle, (e) the surface of a Cy7.5-HSA-PMMA (1.0% P-188) microparticle, and (f) the cross-section of a Cy7.5-HSA-PMMA (1.0% P-188) microparticle. [Diagram 42] Figure 42 is a graph comparing the fluorescence spectra (λex=730 nm) of a Cy7.5 aqueous solution, a Cy7.5-HSA aqueous solution, a Cy7.5-PMMA (no P-188) microparticle dispersion, a Cy7.5-HSA-PMMA (no P-188) microparticle dispersion, and a Cy7.5-HSA-PMMA (1.0% P-188) microparticle dispersion prepared at the same Cy7.5 concentration (30 μM). [Diagram 43] Figure 43 shows scanning electron micrographs of (a) the surface of a Cy7.5-PC (without P-188) microparticle, (b) the cross-section of a Cy7.5-PC (without P-188) microparticle, (c) the surface of a Cy7.5-HSA-PC (without P-188) microparticle, and (d) the cross-section of a Cy7.5-HSA-PC (without P-188) microparticle. [Diagram 44] FIG. 44 is a graph comparing the fluorescence spectra of Cy7.5-PC (without P-188) and Cy7.5-HSA-PC (without P-188) microparticle dispersions prepared at the same Cy7.5 concentration (λex=730 nm). [Diagram 45] FIG. 45 is a graph comparing the fluorescence signal intensity depending on the concentration of Flamma774 and Flamma774-HSA solutions (λex=730 nm, λem=812 nm (Flamma774), λem=818 nm (Flamma774-HSA)). [Figure 46]FIG. 46 shows scanning electron micrographs of (a) the surface of a Flamma774-PMMA (without P-188) microparticle, (b) the cross-section of a Flamma774-PMMA (without P-188) microparticle, (c) the surface of a Flamma774-HSA-PMMA (without P-188) microparticle, (d) the cross-section of a Flamma774-HSA-PMMA (without P-188) microparticle, (e) the surface of a Flamma774-HSA-PMMA (1.0% P-188) microparticle, and (f) the cross-section of a Flamma774-HSA-PMMA (1.0% P-188) microparticle. [Figure 47] FIG. 47 shows fluorescence spectra for comparing the fluorescence signals of Flamma 774 solution, Flamma 774-HSA solution, Flamma 774-PMMA (no P-188) microparticle dispersion, Flamma 774-HSA-PMMA (no P-188) microparticle dispersion, and Flamma 774-HSA-PMMA (1.0% P-188) microparticle dispersion. [Figure 48] FIG. 48 is a graph comparing the fluorescence signal intensity depending on the concentration of Alexa750 and Alexa750-HSA solutions (λex=730 nm, λem=776 nm). [Figure 49] FIG. 49 shows scanning electron micrographs of cross sections of (a) Alexa750-PMMA (no P-188) microparticles, (b) Alexa750-HSA-PMMA (no P-188) microparticles, and (c) Alexa750-HSA-PMMA (1.0% P-188) microparticles. [Figure 50] FIG. 50 is a fluorescence spectrum for comparing the fluorescence signals of Alexa750 solution and Alexa750-HSA solution, Alexa750-PMMA (no P-188) microparticle dispersion, Alexa750-HSA-PMMA (no P-188) microparticle dispersion, and Alexa750-HSA-PMMA (1.0% P-188) microparticle dispersion. [Figure 51] FIG. 51 is a graph comparing the fluorescent signal intensity depending on the concentration of IRDye 800CW and IRDye 800CW-HSA solutions (λex=730 nm, λem=806 nm (IRDye 800CW), λem=810 nm (IRDye 800CW-HSA)). [Figure 52] FIG. 52 shows scanning electron micrographs of (a) IRDye 800CW-PMMA (no P-188) microparticle surface, (b) IRDye 800CW-PMMA (no P-188) microparticle cross-section, (c) IRDye 800CW-HSA-PMMA (no P-188) microparticle surface, (d) IRDye 800CW-HSA-PMMA (no P-188) microparticle cross-section, (e) IRDye 800CW-HSA-PMMA (1.0% P-188) microparticle surface, and (f) IRDye 800CW-HSA-PMMA (1.0% P-188) microparticle cross-section. [Diagram 53] FIG. 53 is a fluorescence spectrum for comparing the fluorescence signals of IRDye 800CW solution and IRDye 800CW-HSA solution, IRDye 800CW-PMMA (no P-188) microparticle dispersion, IRDye 800CW-HSA-PMMA (no P-188) microparticle dispersion, and IRDye 800CW-HSA-PMMA (1.0% P-188) microparticle dispersion. [Figure 54] FIG. 54 is a photograph of ICG-HSA-PLGA (P-188 0.5%) microparticles dispersed in 0.5% sodium methylcellulose / 0.1% Tween 80, 1% sodium alginate, 1% sodium hyaluronate, 2% sodium methylcellulose, 2% poly(vinyl alcohol), 0.1% collagen, 5% gelatin, 10% Tween 80, 40% poloxamer 188, and 5% polyvinyl pyrrolidone aqueous solution to produce a composition in which the microparticles are dispersed in a surfactant or polymer solution. [Figure 55] FIG. 55 is a photograph of cylindrical pellets containing the microparticles produced by dispersing ICG-HSA-PLGA (P-188 0.5%) microparticles in 1% sodium hyaluronate and 5% gelatin aqueous solutions, respectively, and freeze-drying the dispersions. [Figure 56]FIG. 56 is a photograph of ICG-HSA-PMMA (P-188 1.0%) microparticles dispersed in 0.5% sodium methylcellulose / 0.1% Tween 80, 1% sodium alginate, 1% sodium hyaluronate, 2% sodium methylcellulose, 2% poly(vinylalcohol), 0.1% collagen, 5% gelatin, 10% Tween 80, 40% poloxamer-188 (P-188), and 5% polyvinyl pyrrolidone aqueous solutions to produce a composition in which the microparticles are dispersed in a surfactant or polymer solution. [Figure 57] FIG. 57 is a photograph of cylindrical pellets containing ICG-HSA-PMMA (P-188 1.0%) microparticles that were dispersed in an aqueous solution of 1% sodium alginate, 1% sodium hyaluronate, 2% sodium methylcellulose, 2% poly(vinylalcohol), 5% gelatin, 40% poloxamer-188, and 5% polyvinylpyrrolidone, followed by freeze-drying. [Figure 58] FIG. 58 is a photograph of a metal clip coated with fluorescent microparticles, which was prepared by dispersing IRDye 800CW-HSA-PMMA (without P-188) microparticles in a latex solution, coating the surface of the metal clip, and drying. [Figure 59] FIG. 59 is a near-infrared fluorescence image (λex=780 / 20 nm, λem=845 / 40 nm) for a metal clip coated with IRDye 800CW-HSA-PMMA (without P-188) microparticles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0054] The present invention will be described in more detail with reference to the following examples. However, these examples are merely for illustrative purposes and the scope of the present invention is not limited to these examples.

[0055] Example 1: Comparison of the fluorescent signals of indocyanine green solution and indocyanine green / human serum albumin complex

[0056] A near-infrared fluorescent dye, indocyanine green (Diagnogreen Co., Ltd., ICG, Daiichi Pharmaceutical Co., Ltd.), 0.5 mg was dissolved in 1 mL of distilled water and then diluted with distilled water to prepare an indocyanine green solution with a concentration of 30 μM. To compare the fluorescent signal with that of the indocyanine green solution, an indocyanine green / human serum albumin (HSA, SK Plasma) complex was prepared by dissolving 0.5 mg of indocyanine green powder in a mixture of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluting with distilled water to prepare an indocyanine green / human serum albumin complex (ICG-HSA) with a concentration of 30 μM. To compare the fluorescent spectra, 200 μL of each of the prepared solutions was taken and placed in a 96-well plate, and the fluorescent spectra (λ ex = 730 nm).

[0057] Measurement of the fluorescence spectra of indocyanine green solutions and indocyanine green / human serum albumin complex solutions of the same concentration confirmed that the indocyanine green / human serum albumin complex emitted a fluorescence signal 1.5 times higher than that of indocyanine green, as shown in Figure 2.

[0058] Example 2: Preparation and analysis of PLGA microparticles loaded with ICG or ICG-HSA 2-1. Manufacturing of PLGA microparticles loaded with ICG ICG-PLGA (without P-188), which is a PLGA microparticle loaded solely with the near-infrared fluorescent dye indocyanine green, was prepared by the water-in-oil-in-water (W1 / O / W2) emulsion method.

[0059] Specifically, 0.75 mg of indocyanine green (ICG, Selleck chem) was added and dissolved in 1.5 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol (PVA, Sigma-Aldrich) was added to 180 mL of distilled water, and dissolved while stirring at 600 rpm at 85 °C and cooled to room temperature to prepare W2 solution. 1.08 g of poly-D,L-lactide-co-glycolid copolymer (PLGA, MW 192,000-240,000 Da, Evonik) was added and dissolved in 15 mL of dichloromethane (DCM, Sigma-Aldrich) to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 40 seconds using a water bath type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared primary emulsion was added to the prepared W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain particles of PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the microparticles. The washed microparticles were quenched using liquid nitrogen and freeze-dried to obtain microparticle powder.

[0060] 2-2. Preparation of PLGA microparticles loaded with ICG-HSA To prepare PLGA microparticles loaded with indocyanine green / human serum albumin complex (ICG-HSA-PLGA (without P-188)), 0.75 mg of indocyanine green (Diagnogreen strain, Daiichi Pharmaceutical) was dissolved in a mixture of 0.322 mL (20% concentration, 64.335 mg) of human serum albumin (HSA, SK Plasma) and 1.178 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved under stirring at 600 rpm at 85 °C, and cooled to room temperature to prepare W2 solution. 1.08 g of PLGA was added and dissolved in 15 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 40 seconds using a water bath type ultrasonicator to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer while adding the primary W / O emulsion to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the microparticles. The washed microparticles were quenched using liquid nitrogen and freeze-dried to obtain microparticle powder.

[0061] 2-3. Preparation of PLGA microparticles loaded with ICG-HSA containing surfactant (poloxamer) To see the effect of adding a surfactant to the organic solvent phase together with a polymer such as PLGA, microparticles were prepared with a surfactant added to PLGA. To prepare ICG-HSA-loaded PLGA microparticles (ICG-HSA-PLGA (P-188 0.1%)) containing 0.1% (oil phase) of the surfactant Poloxamer 188 (P-188, BASF), 0.75 mg of indocyanine green (Diagnogreen strain, Daiichi Pharmaceutical) was dissolved in a mixture of 0.322 mL (20% concentration, 64.335 mg) of human serum albumin (HSA, SK Plasma) and 1.178 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, dissolved while stirring at 600 rpm at 85°C, and cooled to room temperature to prepare W2 solution. 1.08g of PLGA and 16.5mg of Poloxamer-188 (P-188, BASF) were dissolved in 15mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution and ultrasonicated for 40 seconds using a water bath type ultrasonicator to prepare a primary emulsion (water-in-oil). The prepared primary emulsion was added to the prepared W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain particles of PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were rapidly cooled using liquid nitrogen and freeze-dried to obtain a microparticle powder.

[0062] 2-4. Analysis of indocyanine green content and fluorescence intensity in microparticles In order to evaluate the content and loading rate of indocyanine green in the prepared microparticles, the concentration of indocyanine green in the microparticle dissolution solution was quantified using an ultraviolet / visible light absorption analyzer. 0.5 mg of indocyanine green was dissolved in a mixed solution of 0.214 mL of human serum albumin (20% concentration, 42.89 mg) and 0.786 mL of distilled water to prepare a high-concentration indocyanine green / human serum albumin complex solution. The high-concentration complex solution was diluted with distilled water to prepare standard solutions with 13 concentrations between 0.065 and 6.54 μM. The absorbance of the standard solutions was measured using an ultraviolet / visible light absorption analyzer to prepare a calibration curve, and then 10 mg of PLGA microparticles were dissolved in 1 mL of dimethylsulfoxide (DMSO, Daejung Chemicals & Metals Co. Ltd.) solvent, and the absorbance was analyzed using an ultraviolet / visible light absorption analyzer, and the concentration was measured by substituting it into the calibration curve. The measured complex concentration was substituted into the following equation to evaluate the indocyanine green content and loading efficiency in the microparticles.

[0063] Content of indocyanine green in microparticles = weight of indocyanine green in 10 mg of microparticles / 10 mg (weight of microparticles)

[0064] Indocyanine green loading rate in microparticles = (weight of indocyanine green loaded on entire microparticles / weight of indocyanine green used to load microparticles) x 100%

[0065] The particle morphology and size of the synthesized microparticles were analyzed by scanning electron microscope (JSM-7800F Prime, JEOL Ltd, Japan). The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface via sputtering for 60 seconds, and the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the size of 100 random particles in the obtained photograph and averaging it.

[0066] To compare the fluorescence signals between the microparticles and the indocyanine green / human serum albumin complex, a complex solution and a microparticle dispersion of the same concentration of indocyanine green were prepared. 0.5 mg of indocyanine green powder was dissolved in a mixture of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare an indocyanine green / human serum albumin complex (ICG-HSA) with a concentration of 30 μM. Using the information on the content of indocyanine green in the PLGA microparticles evaluated by the above quantification, a dispersion was prepared by adding 0.3 mL of distilled water to a concentration of indocyanine green of 30 μM. To compare the fluorescence spectra, 200 μL of each of the solutions and dispersions prepared above were taken and placed in a 96-well plate, and the fluorescence spectra (λ ex = 730 nm).

[0067] Quantitative results of indocyanine green in microparticles The loading rate of indocyanine green in ICG-PLGA (without P-188) microparticles was 3.99%, and 43.6 ng was loaded per 1 mg of microparticles. In the case of ICG-HSA-PLGA (without P-188) microparticles, the loading rate was 8.39%, and the content of indocyanine green in 1 mg of microparticles was 93.6 ng. In the case of ICG-HSA-PLGA (P-188 0.1%) manufactured under the condition of 0.1% poloxamer-188 content based on the primary emulsion phase during ICG-HSA-PLGA synthesis, the loading rate of indocyanine green was 5.26%, and the content of indocyanine green in 1 mg of microparticles was reduced to 59.7 ng compared to ICG-HSA-PLGA (without P-188). This is believed to be because poloxamer-188, which has both hydrophilic and hydrophobic functional groups, is evenly distributed on the PLGA, distributing the hydrophilic indocyanine green / human serum complex evenly on the PLGA, while at the same time forming a passageway through which water can pass, allowing some of the fluorescent dye to dissolve during the synthesis process.

[0068] Scanning electron micrographs confirmed that the particle morphology of the three microparticles was spherical (Figure 3, (a) ICG-PLGA, (b) ICG-HSA-PLGA, (c) ICG-HSA-PLGA (P-188 0.1%)). The average particle sizes were 67.5 ± 24.6 μm, 85.4 ± 28.7 μm, and 77.5 ± 20.2 μm for ICG-PLGA (without P-188), ICG-HSA-PLGA (without P-188), and ICG-HSA-PLGA (P-188 0.1%), respectively, confirming that all particles were 20 μm or larger, which is sufficient to avoid macrophage action.

[0069] As can be seen from the fluorescence spectrum (Figure 4), the ICG-PLGA (without P-188) microparticle dispersion, in which ICG was loaded alone, showed a 6.8-fold lower fluorescent signal than ICG-HSA. This is because when indocyanine green is loaded onto PLGA, the fluorescent dye cannot be prevented from agglomerating, resulting in a signal reduction effect. In the ICG-HSA-PLGA (without P-188) and ICG-HSA-PLGA (0.1% P-188) microparticle dispersions, the fluorescent signal was reduced by 2.8-fold compared to ICG-HSA, but was 2.4-fold higher than ICG-PLGA (without P-188). This confirmed that a surgical marker microparticle with a higher fluorescent signal can be obtained by loading ICG onto PLGA in the form of ICG-HSA, compared to loading ICG alone onto PLGA. This is because HSA can prevent ICG from agglomerating, thereby partially preventing the reduction in the fluorescent signal. Microparticles prepared to contain 0.1% poloxamer-188 showed similar fluorescence intensity to PLGA microparticles loaded with ICG-HSA without poloxamer-188, and showed a higher fluorescence signal compared to ICG-PLGA microparticles.

[0070] Example 3: Preparation of ICG-HSA-PLGA microparticles with different poloxamer-188 concentrations and fluorescence intensity analysis 3-1. Production of microparticles and experimental methods In this example, microparticles were prepared by increasing the concentration of poloxamer-188, and the effect on the fluorescence intensity of the microparticles was observed. In order to prepare ICG-HSA-loaded PLGA microparticles (ICG-HSA-PLGA (P-188 0.5%)) containing 0.5% (oil phase) of poloxamer-188 (Poloxamer 188, P-188, BASF) based on the primary emulsion phase, 0.75 mg of indocyanine green was dissolved in a mixed solution of 0.322 mL of human serum albumin (20% concentration, 64.335 mg) and 1.178 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and then dissolved while stirring at 600 rpm under the condition of 85 ° C., and cooled to room temperature to prepare W2 solution. 1.08g of PLGA and 82.5mg of poloxamer-188 were dissolved in 15mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution and then ultrasonicated for 40 seconds using a water bath type ultrasonicator to prepare a primary emulsion (water-in-oil). The prepared primary emulsion was added to the prepared W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature of 40°C for 21 hours to remove the methylene chloride solvent. Then, the mixture was centrifuged at 14,000 rpm for 5 minutes to obtain particles of PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the microparticles. The washed microparticles were rapidly cooled using liquid nitrogen and then freeze-dried to obtain a microparticle powder.

[0071] To prepare ICG-HSA-loaded PLGA microparticles (ICG-HSA-PLGA (P-188 1.0%)) containing 1.0% (oil phase) poloxamer-188 based on the primary emulsion phase, 0.75 mg of indocyanine green was dissolved in a mixed solution of 0.322 mL of human serum albumin (20% concentration, 64.335 mg) and 1.178 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved under stirring at 600 rpm at 85 ° C., and cooled to room temperature to prepare W2 solution. 1.08 g of PLGA and 165 mg of poloxamer-188 were added and dissolved in 15 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 40 seconds using a water bath type ultrasonicator to prepare a primary emulsion (water-in-oil). The primary emulsion was prepared by adding the prepared W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature of 40°C to remove the methylene chloride solvent. Then, the mixture was centrifuged at 14,000 rpm for 5 minutes to obtain PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the mixture was redispersed by adding distilled water, followed by centrifugation three times to wash the microparticles. The washed microparticles were quenched using liquid nitrogen and freeze-dried to obtain microparticle powder.

[0072] In order to evaluate the content and loading rate of indocyanine green in the prepared microparticles, the concentration of indocyanine green in the microparticle dissolution solution was quantified using an ultraviolet / visible light absorption analyzer. 0.5 mg of indocyanine green was dissolved in a mixed solution of 0.214 mL of human serum albumin (20% concentration, 42.89 mg) and 0.786 mL of distilled water to prepare a high-concentration indocyanine green / human serum albumin complex solution. The high-concentration complex solution was diluted with distilled water to prepare 13 standard solutions of concentrations between 0.065 and 6.54 μM. The absorbance of the standard solution was measured using an ultraviolet / visible light absorption analyzer to create a calibration curve, and then 10 mg of PLGA microparticles were dissolved in 1 mL of dimethyl sulfoxide solvent, and the absorbance was analyzed using an ultraviolet / visible light absorption analyzer, and the concentration was measured by substituting it into the calibration curve. The measured complex concentration was substituted into the following formula to evaluate the indocyanine green content and loading efficiency in the microparticles.

[0073] Scanning electron microscopy was performed to analyze the particle morphology and size of the synthesized microparticles. For cross-sectional analysis of the produced microparticles, the microparticle powder was crushed with a razor blade. The microparticle powder for measuring the microparticle surface and cross-section was attached to a carbon tape attached to a scanning electron microscope sample holder, and then Pt / Pd was coated on the surface by sputtering for 60 seconds, and the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0074] To compare the fluorescent signals between the microparticles and the indocyanine green / human serum albumin complex, a complex solution and a microparticle dispersion of indocyanine green at the same concentration were prepared. 0.5 mg of indocyanine green powder was dissolved in a mixed solution of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of indocyanine green / human serum albumin complex (ICG-HSA) at a concentration of 30 μM. Using the information on the content of indocyanine green in the PLGA microparticles evaluated by the above quantification, 0.3 mL of distilled water was added to make the concentration of indocyanine green 30 μM to prepare a dispersion. To compare the fluorescent spectra, 200 μL of each of the prepared solutions and dispersions were taken and placed in a 96-well plate, and the fluorescent spectra (λ ex Fluorescence images were analyzed (λ = 730 nm) using a fluorescence imaging device (IVIS Lumina XR, Xenogen Corporation-Caliper, CA, USA) after placing 300 μL of the same solution in a microtube. ex = 780 / 20 nm, λ em =845 / 40 nm).

[0075] To evaluate the fluorescence persistence of the surgical marker microparticles in an animal model, 100 μL of an ICG-HSA solution with a concentration of 30 μM ICG and the microparticle dispersion, which were prepared using injectable saline containing 0.5% sodium carboxymethyl cellulose (Sigma-Aldrich) and 0.1% Tween 80 (Sigma-Aldrich), were subcutaneously injected into SKH-1 hairless mice (Orient Bio Co., Ltd.) using a 1 mL syringe (21G needle), and the time-dependent fluorescence signal was photographed (λ = 0.01 μm) using a fluorescence imaging device (IVIS Lumina XR). ex = 780 / 20 nm, λ em =845 / 40 nm).

[0076] 3-2. Comparative analysis of indocyanine green loading rate and fluorescence intensity The ICG loading rate in ICG-HSA-PLGA (P-188 0.5%) microparticles, which was prepared by increasing the concentration of poloxamer-188 in the primary emulsion phase to 0.5%, was 13.8%, and the indocyanine green content in 1 mg of microparticles was 124.2 ng, confirming that the loading rate and content of indocyanine green were increased compared to ICG-HSA-PLGA (P-188 0.1%). The concentration of poloxamer-188 in the primary emulsion phase standard during the production of ICG-HSA-PLGA microparticles was increased to 1.0%. The loading rate of ICG in the ICG-HSA-PLGA (P-188 1.0%) microparticles was 8.71%, and the content of indocyanine green in 1 mg of microparticles was 72.7 ng, confirming that the loading rate and content of indocyanine green were higher than those of ICG-HSA-PLGA (P-188 0.1%).

[0077] Scanning electron microscopy of ICG-HSA-PLGA (P-188 0.5%) and ICG-HSA-PLGA (P-188 1.0%) microparticles showed that the two microparticles were spherical with average particle sizes of 59.8 ± 19.6 μm and 68.0 ± 27.6 μm, respectively (Figure 5, (a, b: ICG-HSA-PLGA (P-188 0.5%), c, d: ICG-HSA-PLGA (P-188 1.0%)), and the cross-sections of both microparticles were evaluated using a scanning electron microscope, and it was confirmed that the PLGA microparticles had multiple small spherical spaces inside. In the case of PLGA microbubbles, the surface is thin, and when the surface decomposes and holes are formed, the dye loaded inside the microbubbles is rapidly dissolved, whereas in the case of the microparticles produced by the present invention, when multiple spherical spaces loaded with dye are isolated from each other, even if the surface of the microparticles is partially decomposed and holes are formed, it is possible to prevent the loaded fluorescent dye from dissolving, and the fluorescent dye can be maintained at a high concentration in the microparticles for a long period of time at the labeled site.

[0078] In the fluorescence spectra of the ICG-HSA-PLGA (P-188 0.5%) and ICG-HSA-PLGA (P-188 1.0%) dispersions in Figure 6, the fluorescence signals were 2.1 and 3.6 times higher than ICG-HSA, and 14 and 25 times higher than ICG-PLGA (no P-188), respectively. This result shows that when microparticles are produced containing 0.5% or more poloxamer-188 based on the primary emulsion phase, a very high fluorescence signal can be obtained.

[0079] Even when the microparticle dispersion was photographed with a fluorescent imaging device (Figure 7, a: ICG-HSA, b: ICG-HSA-PLGA (P-188 0.5%), c: ICG-HSA-PLGA (P-188 1.0%)), it was confirmed that strong fluorescent signals were generated for ICG-HSA-PLGA (P-188 0.5%) and ICG-HSA-PLGA (P-188 1.0%) microparticles.

[0080] Figure 8 shows the time-dependent fluorescence images (λ ex = 780 / 20 nm, λ em = 845 / 40 nm). When ICG-HSA was injected, there was intense fluorescence bleeding at the injection site, and it was confirmed that the fluorescence signal was hardly detected from one day after injection (Fig. 8-a). On the other hand, in the case of ICG-HSA-PLGA (P-188 0.5%) (Fig. 8-b) and ICG-HSA-PLGA (P-188 1.0%) (Fig. 8-c) microparticle dispersions, the fluorescence signal generated in the labeled area decreased slightly until the first day, but by the 30th day, there was no bleeding of the fluorescence signal and a strong fluorescence signal was maintained, and it was possible to clearly confirm the labeled area from the fluorescence image.

[0081] The ROI values ​​for the fluorescent signals at the labeled sites analyzed from the fluorescent image photographs are shown in Figure 9. In the case of ICG-HSA, it was confirmed that the fluorescent signals rapidly decreased after injection, with the fluorescence decreasing to a level of 6.4% after 1 day and almost disappearing after 2 days.

[0082] In the case of ICG-HSA-PLGA (P-188 0.5%) and ICG-HSA-PLGA (P-188 1.0%) microparticle dispersions, the highest fluorescence intensity was observed at 5 hours, and after 1 day, 46% and 65% of the fluorescence remained, respectively, and after 30 days, 26% and 48% of the fluorescence remained. From these results, it was confirmed that in the case of ICG-HSA-PLGA (P-188 0.5%) and ICG-HSA-PLGA (P-188 1.0%) microparticles, there was no bleeding of the fluorescent dye at the labeled site, and a strong fluorescent signal could be maintained for more than 30 days.

[0083] Example 4: Preparation and analysis of microparticles using polymers other than PLGA 4-1: Preparation and analysis of microparticles using PLGA and PDLLA-PEG block copolymers Poly(D,L-lactide)-block-poly(ethylene glycol), PDLLA-PEG (Sigma-Aldrich) was used to prepare the microparticles, with molecular weights of the PDLLA and PEG blocks of 20,000 and 5,000 Da, respectively. To prepare ICG-HSA-Alginate-PLGA and PDLLA-PEG (P-188 0.1%) microparticles, 0.75 mg of indocyanine green (ICG) was dissolved in 0.322 mL of human serum albumin (HSA) (20% concentration, 64.335 mg) and 0.278 mL of distilled water, and a solution of 6 mg of sodium alginate (Soidum Alginate, ALG, Kimica) dissolved in 0.6 mL of distilled water was mixed to prepare W1 solution. 3.6g of polyvinyl alcohol was added to 180mL of distilled water, and dissolved at 85℃ under stirring at 600 rpm, then cooled to room temperature to prepare W2 solution. 1.08g of PLGA, 0.12mg of PDLLA-PEG, and 16.5mg of poloxamer-188 (P-188) were added to 15mL of methylene chloride and dissolved to prepare an oil solution. The prepared W1 solution was added to the oil solution and sonicated for 40 seconds using a water bath type ultrasonicator. 0.3mL of calcium chloride (CaCl2, Sigma-Aldrich) at a concentration of 4.304mg / mL was further added and sonicated for 40 seconds to prepare a primary emulsion (water-in-oil) in which alginic acid dissolved in the W1 phase caused ionic crosslinking and gelation. The primary emulsion was added to W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at 40°C for 21 hours to remove the methylene chloride solvent. The mixture was then centrifuged at 14,000 rpm for 5 minutes to obtain PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and distilled water was added to redisperse the mixture, followed by repeating the centrifugation process three times to wash the microparticles.The washed microparticles were freeze-dried to finally obtain ICG-HSA-Alginate-PLGA, PDLLA-PEG (P-188 0.1%) microparticle powders.

[0084] To evaluate the content and loading rate of indocyanine green in the prepared microparticles, the microparticles were dissolved, and the concentration of indocyanine green in the solution was quantified using an ultraviolet / visible light absorption spectrometer.

[0085] Scanning electron microscopy was performed to analyze the particle morphology and size of the synthesized microparticles. For cross-sectional analysis of the prepared microparticles, the microparticles were cut with a razor blade. The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface by sputtering for 60 seconds, and then the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0086] To compare the fluorescent signals between the microparticles and the indocyanine green / human serum albumin complex, a complex solution and a microparticle dispersion of indocyanine green with the same concentration were prepared. 0.5 mg of indocyanine green powder was dissolved in a mixed solution of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of indocyanine green / human serum albumin complex (ICG-HSA) with a concentration of 30 μM. Using the information on the content of indocyanine green in the PLGA and PDLLA-PEG microparticles evaluated by the above quantification, 0.3 mL of distilled water was added to prepare a microparticle dispersion so that the concentration of indocyanine green was 30 μM. To compare the fluorescent spectra, 200 μL of each of the solutions and microparticle dispersions prepared above were taken and placed in a 96-well plate, and the fluorescent spectra (λ ex Fluorescence images were analyzed (λ = 730 nm) using a fluorescence imaging device (IVIS Lumina XR) after placing 300 μL of the same solution in a microtube. ex= 780 / 20 nm, λ em =845 / 40 nm).

[0087] To evaluate the change in fluorescence intensity of injected microparticles from an animal model, a microparticle dispersion was prepared using injectable saline containing 0.5% sodium carboxymethyl cellulose (Sigma-Aldrich) and 0.1% Tween 80 (Sigma-Aldrich), and 100 μL of such dispersion was injected subcutaneously into SKH-1 hairless mice. The fluorescence signal over time was photographed (λ 0.01 mm) using a fluorescence imaging device (IVIS Lumina XR). ex = 780 / 20 nm, λ em =845 / 40 nm).

[0088] The indocyanine green loading rate of the ICG-HSA-Alginate-PLGA and PDLLA-PEG (P-188 0.1%) microparticles was 15.8%, and the indocyanine green content per 1 mg of microparticles was 234.6 ng, confirming that the indocyanine green content was increased compared to conventional conditions.

[0089] The ICG-HSA-Alginate-PLGA and PDLLA-PEG (P-188 0.1%) microparticles were spherical particles with an average particle diameter of 74.3 ± 18.2 μm, and were confirmed to have an appropriate size to avoid phagocytosis by macrophages (Figure 10(a)). In addition, the scanning electron micrograph of the particle cross section (Figure 10(b)) showed that the interior of the particle contained multiple isolated small spherical spaces, similar to ICG-HSA-PLGA (P-188 0.5%) and ICG-HSA-PLGA (P-188 1.0%), which prevented the elution of the loaded fluorescent dye, and confirmed that the morphology was very suitable for long-term fluorescent dye labeling.

[0090] The fluorescence spectra of the ICG-HSA-Alginate-PLGA and PDLLA-PEG (P-188 0.1%) microparticle dispersions in Figure 11 confirmed fluorescent signals that were 2.3 times higher than ICG-HSA and 15 times higher than ICG-PLGA (without P-188).

[0091] Comparison of the fluorescence images of the microparticle dispersions (Figure 12) confirmed that the fluorescence signals of the ICG-HSA-Alginate-PLGA and PDLLA-PEG (P-188 0.1%) microparticle dispersions (Figure 12-b) were higher than that of the ICG-HSA solution (Figure 12-a).

[0092] Figure 13 shows the time-dependent fluorescence images (λ) of ICG-HSA solution, ICG-HSA-Alginate-PLGA, and PDLLA-PEG (P-188 0.1%) microparticle dispersions subcutaneously injected into SKH-1 hairless mice. ex = 780 / 20 nm, λ em =845 / 40 nm). In the case of ICG-HSA, the fluorescent signal was observed for up to 5 hours, and it was confirmed that the fluorescent signal was not observed after 1 day (Figure 13-a). On the other hand, in the case of ICG-HSA-Alginate-PLGA and PDLLA-PEG (P-188 0.1%) microparticle dispersions (Figure 13-b), the fluorescently labeled area gradually decreased after 7 days, but the fluorescent signal was maintained at a high level until 30 days. The ROI values ​​analyzed from the fluorescent image photographs were shown in a graph (Figure 14). Unlike ICG-HSA, when ICG-HSA-Alginate-PLGA and PDLLA-PEG (P-188 0.1%) microparticles were administered, 79% of the fluorescent signal was maintained after 1 day and 32% of the fluorescent signal was maintained after 30 days. This confirmed that the use of ICG-HSA-Alginate-PLGA and PDLLA-PEG (P-188 0.1%) microparticles allows fluorescent labeling of the lesion site for more than 30 days.

[0093] Example 4-2: Production and analysis of microparticles using PMMA polymer To prepare PMMA microparticles, ICG-HSA-PMMA (P-188 1.0%) microparticles were prepared using poly(methyl methacrylate), PMMA (MW 120,000 Da, Sigma-Aldrich) polymer. W1 solution was prepared by dissolving 0.75 mg of indocyanine green (ICG) in a mixture of 0.322 mL of human serum albumin (HSA) (20% concentration, 64.335 mg) and 1.178 mL of distilled water. W2 solution was prepared by adding 3.6 g of polyvinyl alcohol to 180 mL of distilled water and dissolving it under stirring at 600 rpm at 85 °C and cooling to room temperature. PMMA 1.08 g and poloxamer-188 (P-188) 165 mg were added and dissolved in 15 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 30 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PMMA microparticles. The washed microparticles were freeze-dried to obtain microparticle powder.

[0094] To evaluate the content and loading rate of indocyanine green in the prepared microparticles, the microparticles were dissolved, and the concentration of indocyanine green in the solution was quantified using an ultraviolet / visible light absorption spectrometer.

[0095] Scanning electron microscopy was performed to analyze the particle morphology and size of the synthesized microparticles. For cross-sectional analysis of the prepared microparticles, the microparticles were cut with a razor blade. The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface by sputtering for 60 seconds, and then the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0096] To compare the fluorescent signals between the prepared microparticles and the indocyanine green / human serum albumin complex, an indocyanine green complex solution and a microparticle dispersion of the same concentration were prepared. 0.5 mg of indocyanine green powder was dissolved in a mixed solution of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of indocyanine green / human serum albumin complex (ICG-HSA) with a concentration of 30 μM. Using the information on the content of indocyanine green in the PMMA microparticles evaluated by the above quantification, 0.3 mL of distilled water was added to prepare a microparticle dispersion so that the concentration of indocyanine green was 30 μM. To compare the fluorescent spectra, 200 μL of each of the prepared solutions and microparticle dispersions were taken and placed in a 96-well plate, and the fluorescent spectra (λ ex Fluorescence images were analyzed (λ = 730 nm) using a fluorescence imaging device (IVIS Lumina XR) after placing 300 μL of the same solution in a microtube. ex = 780 / 20 nm, λ em =845 / 40 nm).

[0097] To evaluate the change in fluorescence intensity of injected microparticles from an animal model, a microparticle dispersion was prepared using injectable saline containing 0.5% sodium carboxymethyl cellulose (Sigma-Aldrich) and 0.1% Tween 80 (Sigma-Aldrich), and 100 μL of such dispersion was injected subcutaneously into SKH-1 hairless mice. The fluorescence signal over time was photographed (λ 0.01 mm) using a fluorescence imaging device (IVIS Lumina XR). ex = 780 / 20 nm, λ em =845 / 40 nm).

[0098] The indocyanine green loading rate of the ICG-HSA-PMMA (P-188 1.0%) microparticles was 44.0%, and the indocyanine green content per 1 mg of microparticles was high at 370.3 ng.

[0099] The ICG-HSA-PMMA (P-188 1.0%) microparticles were confirmed to be spherical particles with an average particle diameter of 49.0 ± 18.7 μm, which is an appropriate size to avoid phagocytosis by macrophages (Figure 15(a)). In addition, a scanning electron microscope photograph of the particle cross section (Figure 15(b)) showed that the inside of the particle contains multiple isolated small spherical spaces, which can prevent the elution of the fluorescent dye loaded in these spaces, and it was confirmed that this form is very suitable for long-term fluorescent dye labeling.

[0100] The fluorescence spectrum of the ICG-HSA-PMMA (P-188 1.0%) microparticle dispersion in Figure 16 shows a fluorescence signal of the same level as ICG-HSA, but 7 times higher than ICG-PLGA (no P-188).

[0101] A comparison of the fluorescence images of the ICG-HSA-PMMA (P-188 1.0%) microparticle dispersion (FIG. 17) confirmed that it generated a high fluorescence signal similar to that of the ICG-HSA solution.

[0102] Figure 18 shows the time-dependent fluorescence images (λ ex = 780 / 20 nm, λ em Unlike ICG-HSA (Figure 18-a), when ICG-HSA-PMMA (P-188 1.0%) microparticles (Figure 18-b) were administered, there was no bleeding of the fluorescent dye, and a high fluorescent signal was maintained for up to 30 days.

[0103] The ROI values ​​analyzed from the fluorescent image photographs were plotted in a graph (Figure 19). Unlike ICG-HSA, in the case of the ICG-HSA-PMMA (P-188 1.0%) microparticle dispersion, 55% of the fluorescence remained after 1 day, and 36% of the fluorescence intensity was maintained after 30 days. From these results, it was confirmed that ICG-HSA-PMMA (P-188 1.0%) microparticles are useful as a fluorescent marker that can maintain a fluorescent signal for more than 30 days in the labeled lesion.

[0104] From the above examples, it was confirmed that when microparticles are manufactured by loading ICG alone, microparticles that generate a very weak fluorescent signal are obtained, whereas when microparticles are manufactured using an ICG-HSA complex or when ICG-HSA is mixed with an alginate polymer and then gelled via ionic crosslinking, microparticles that generate a strong fluorescent signal can be manufactured.

[0105] Example 5: Preparation and analysis of ICG-loaded PLGA microparticles using alginic acid hydrate gel In this example, ICG was mixed with alginic acid to prepare W1 solution, and it was analyzed whether the fluorescent signal of ICG-loaded microparticles could be increased even when alginic acid was ionically crosslinked using calcium. In order to prepare PLGA microparticles (ICG-Alginate-PLGA (without P-188)) in which ICG is contained in an alginic acid hydrate gel, a solution in which 0.75 mg of indocyanine green (ICG) was dissolved in 0.6 mL of distilled water was mixed with a solution in which 6 mg of sodium alginate (Soidum Alginate) was dissolved in 0.6 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and then dissolved while stirring at 600 rpm under conditions of 85 °C, and cooled to room temperature to prepare W2 solution. 1.08 g of PLGA was added and dissolved in 15 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution and sonicated for 40 seconds using a water bath type ultrasonicator. To induce ionic crosslinking of alginic acid, 0.3 mL of calcium chloride (CaCl2, Sigma-Aldrich) at a concentration of 4.304 mg / mL was further added and sonicated for 40 seconds to prepare a primary emulsion (water-in-oil) in which alginic acid was gelled. The prepared primary emulsion was added while stirring the W2 solution at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain ICG-Alginate-PLGA (without P-188) particles, which are PLGA polymeric microparticles loaded with indocyanine green. The supernatant was removed, and the microparticles were washed by repeating the process of adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain a microparticle powder.

[0106] Next, ICG-Alginate-PLGA (P-188 0.1%) microparticles were prepared by further mixing poloxamer-188 (P-188) at 0.1% (oil phase) based on the primary emulsion phase. W1 solution was prepared by mixing a solution of 0.75 mg of indocyanine green (ICG) dissolved in 0.6 mL of distilled water with a solution of 6 mg of sodium alginate dissolved in 0.6 mL of distilled water. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, dissolved at 85 ° C while stirring at 600 rpm, and cooled to room temperature to prepare W2 solution. 1.08 g of PLGA and 16.5 mg of poloxamer-188 (P-188) were added to 15 mL of methylene chloride and dissolved to prepare an oil solution. The prepared W1 solution was added to the oil solution and sonicated for 40 seconds in a water bath type ultrasonicator. In order to induce the formation of ionic cross-linking bonds of the alginic acid polymer, 0.3 mL of calcium chloride (CaCl2, Sigma-Aldrich) at a concentration of 4.304 mg / mL was further added and sonicated for 40 seconds to prepare a primary emulsion in which alginic acid was gelled. The prepared primary emulsion was added to the W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, the mixture was centrifuged at 14,000 rpm for 5 minutes to obtain particles of PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the microparticles. The washed microparticles were freeze-dried to obtain a microparticle powder.

[0107] To evaluate the content and loading rate of indocyanine green in the prepared microparticles, the concentration of indocyanine green in the microparticle dissolution solution was quantified using an ultraviolet / visible light absorption spectrometer. 10 mg of PLGA microparticles were placed in 1 mL of dimethylsulfoxide (DMSO) solvent, and the absorbance of the dissolved solution was analyzed using an ultraviolet / visible light absorption spectrometer. The concentration of indocyanine green was measured by comparing with a standard calibration curve.

[0108] The synthesized microparticles were analyzed for particle morphology and size by scanning electron microscope (JSM-7800F Prime). The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface by sputtering for 60 seconds, and the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0109] To compare the fluorescent signals between the microparticles and the indocyanine green / human serum albumin complex, a complex solution and a microparticle dispersion of indocyanine green of the same concentration were prepared. 0.5 mg of indocyanine green powder was dissolved in a mixture of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of indocyanine green / human serum albumin complex (ICG-HSA) with a concentration of 30 μM. Using the information on the content of indocyanine green in the PLGA microparticles evaluated by the above quantification, 0.3 mL of distilled water was added to the indocyanine green concentration of 30 μM to prepare a microparticle dispersion. To compare the fluorescent spectra, 200 μL of each of the solutions and microparticle dispersions prepared above were taken and placed in a 96-well plate, and the fluorescent spectra (λ ex = 730 nm).

[0110] The loading rate of indocyanine green in ICG-Algiante-PLGA (without P-188) microparticles was 5.79%, and the content of indocyanine green in 1 mg of microparticles was 69.0 ng. In the case of ICG-Algiante-PLGA (P-188 0.1%) microparticles with 0.1% poloxamer-188 added based on the primary emulsion phase, the loading rate of indocyanine green increased to 9.21%, and the content of indocyanine green in 1 mg of microparticles also increased to 84.3 ng.

[0111] In the scanning electron micrographs of Figure 20, it was confirmed that the two microparticles, ICG-Algiante-PLGA (without P-188) and ICG-Algiante-PLGA (0.1% P-188), were spherical particles with average particle sizes of 84.5±33.2 μm and 70.2±21.1 μm, respectively, thereby effectively avoiding the phagocytosis of macrophages.

[0112] The fluorescence spectra of ICG-Algiante-PLGA (without P-188) and ICG-Algiante-PLGA (0.1% P-188) microparticle dispersions in Figure 21 show that, compared to ICG-PLGA (without P-188) microparticles, the ICG-Algiante-PLGA (without P-188) microparticles showed a slight increase in fluorescence, while the ICG-Algiante-PLGA (0.1% P-188) microparticles showed a 5-fold higher fluorescence signal. This result indicates that when poloxamer-188 is added to the alginate gelation conditions, microparticles showing a high fluorescence signal can be produced.

[0113] Example 6: Preparation and analysis of PLGA microparticles containing ICG-HSA mixed with alginic acid hydrate gel Polymer microparticles were prepared by mixing the ICG-HSA complex with alginate polymer and ionically cross-linking the alginate polymer with calcium, and the fluorescent signals were analyzed.

[0114] To prepare ICG-HSA-Alginate-PLGA (P-188 0.1%) microparticles, which are ICG-HSA-loaded PLGA microparticles in which alginic acid was mixed with ICG-HSA and poloxamer-188 (P-188) was added to the oil phase, a solution was prepared by mixing 75 mg of indocyanine green (ICG) with 0.322 mL of human serum albumin (HSA) (20% concentration, 64.335 mg) and 0.278 mL of distilled water, and a solution of 6 mg of sodium alginate (Soidum Alginate, ALG, Kimica) dissolved in 0.6 mL of distilled water was mixed to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, dissolved while stirring at 600 rpm at 85 °C, and cooled to room temperature to prepare W2 solution. 1.08 g of PLGA and 16.5 mg of poloxamer-188 (P-188) were dissolved in 15 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution and sonicated for 40 seconds using a water bath type ultrasonicator, and 0.3 mL of calcium chloride (CaCl2, Sigma-Aldrich) at a concentration of 4.304 mg / mL was further added and sonicated for 40 seconds to prepare a primary emulsion (water-in-oil) in which alginic acid was gelled. The primary emulsion was added to the W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40 ° C for 21 hours to remove the methylene chloride solvent. Then, the mixture was centrifuged at 14,000 rpm for 5 minutes to obtain PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0115] To prepare ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticles, which are ICG-HSA-loaded PLGA microparticles in which alginic acid was mixed with ICG-HSA and poloxamer-188 (P-188) was added to the oil phase, a solution was prepared by mixing 75 mg of indocyanine green (ICG) with 0.322 mL of human serum albumin (HSA) (20% concentration, 64.335 mg) and 0.278 mL of distilled water, and a solution of 6 mg of sodium alginate (Soidum Alginate, ALG, Kimica) dissolved in 0.6 mL of distilled water was mixed to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, dissolved while stirring at 600 rpm at 85 °C, and cooled to room temperature to prepare W2 solution. 1.08 g of PLGA and 82.5 mg of poloxamer-188 (P-188) were dissolved in 15 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 40 seconds using a water bath type ultrasonicator. 0.3 mL of calcium chloride (CaCl2, Sigma-Aldrich) at a concentration of 4.304 mg / mL was added and further ultrasonicated for 40 seconds to prepare a primary emulsion (water-in-oil) in which alginic acid was gelled. The primary emulsion was added to the W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40 ° C for 21 hours to remove the methylene chloride solvent. Then, the mixture was centrifuged at 14,000 rpm for 5 minutes to obtain PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0116] The content and loading rate of indocyanine green in the prepared microparticles were analyzed.

[0117] The synthesized microparticles were analyzed by scanning electron microscope to observe their particle morphology, size, and cross-sectional shape. The particle size was calculated by averaging the particle sizes of 100 randomly selected particles in the obtained photograph.

[0118] To compare the fluorescent signals of the prepared microparticles and the indocyanine green / human serum albumin complex, an indocyanine green complex solution and a microparticle dispersion were prepared at the same concentration. To compare the fluorescent spectra, 200 μL of each of the prepared solutions and the microparticle dispersion were taken and placed in a 96-well plate, and the fluorescent spectra (λ ex Fluorescence images were analyzed (λ = 730 nm) using a fluorescence imaging device (IVIS Lumina XR) after placing 300 μL of the same solution in a microtube. ex = 780 / 20 nm, λ em =845 / 40 nm).

[0119] In order to evaluate the efficacy of fluorescent labeling of the fluorescent marker microparticles in an animal model, the ICG-HSA solution with a concentration of 30 μM ICG and the microparticles were dispersed in saline for injection containing 0.5% sodium carboxymethyl cellulose (Sigma-Aldrich) and 0.1% Tween 80 (Sigma-Aldrich). 100 μL of the microparticle dispersion was subcutaneously injected into SKH-1 hairless mice using a syringe, and the fluorescent signal over time was photographed (λ = 0.01 μm) using a fluorescent imaging device (IVIS Lumina XR). ex = 780 / 20 nm, λ em =845 / 40 nm).

[0120] The loading rates of indocyanine green in ICG-HSA-Alginate-PLGA (P-188 0.1%) and ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticles were 10.5% and 7.62%, respectively, and the indocyanine green contents in 1 mg of microparticles were analyzed to be 108.7 ng and 61.6 ng.

[0121] The ICG-HSA-Alginate-PLGA (P-188 0.1%) and ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticles were confirmed to be spherical particles with average particle diameters of 77.8±26.5μm and 67.9±24.1μm (Figure 22), which are suitable sizes for avoiding phagocytosis by macrophages. In addition, as can be seen from the cross-sectional photograph of the microparticles in Figure 22(c), the inside of the microparticles is composed of multiple isolated spherical spaces, which shows that the release of fluorescent dye can be suppressed better than with a microbubble-shaped structure.

[0122] Comparison of the fluorescent signals based on the fluorescence spectra in Figure 23 revealed that ICG-HSA-Alginate-PLGA (P-188 0.1%) showed a fluorescent signal similar to that of ICG-HSA, and a fluorescent signal 6.4 times higher than that of ICG-PLGA (without P-188), while ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticles showed a fluorescent signal 2.5 times higher than that of ICG-HSA, and a fluorescent signal 17 times higher than that of ICG-PLGA (without P-188).

[0123] Fluorescence image photographs (Figure 24) also confirmed that the prepared ICG-HSA-Alginate-PLGA (P-188 0.1%) (Figure 8C-b) and ICG-HSA-Alginate-PLGA (P-188 0.5%) (Figure 8C-c) microparticle dispersions emitted strong fluorescent signals.

[0124] FIG. 25 shows the results of subcutaneous injection of an ICG-HSA solution and an ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticle dispersion into SKH-1 hairless mice, and then capturing fluorescence images over time (λ ex = 780 / 20 nm, λ em = 845 / 40 nm. Unlike the case of ICG-HSA (Figure 25-a), where no fluorescent signal was observed after one day, it was confirmed that a high fluorescent signal was maintained up to 30 days after administration of the ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticle dispersion (Figure 25-b).

[0125] The ROI values ​​analyzed from the fluorescent image photographs were plotted in a graph (Figure 26). It was confirmed that in the case of the ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticle dispersion, 80% of the fluorescence remained one day after administration, and a high fluorescent signal of 46% was observed even after 30 days.

[0126] These results confirmed that the ICG-HSA-Alginate-PLGA (P-188) microparticles were highly useful as fluorescent markers.

[0127] Example 7: Preparation and analysis of microparticles using Tween as a surfactant In this example, to show that other types of surfactants can be used instead of the surfactant P-188, microparticles were prepared using Tween and analyzed. W1 solution was prepared by mixing 0.75 mg of indocyanine green (ICG) with 0.322 mL of human serum albumin (HSA) (20% concentration, 64.335 mg) and 0.278 mL of distilled water and 6 mg of sodium alginate dissolved in 0.6 mL of distilled water. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, dissolved while stirring at 600 rpm at 85°C, and cooled to room temperature to prepare W2 solution. 1.08 g of PLGA and 82.5 mg of Tween (Sigma-Aldrich) were added to 15 mL of methylene chloride and dissolved to prepare an oil solution. The prepared W1 solution was added to the oil solution, and sonicated for 40 seconds using a water bath type ultrasonicator. 0.3 mL of calcium chloride (CaCl2, Sigma-Aldrich) with a concentration of 4.304 mg / mL was further added and sonicated for 40 seconds to prepare a primary emulsion (water-in-oil) in which alginic acid was gelled. The primary emulsion was added to the W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, the mixture was centrifuged at 14,000 rpm for 5 minutes to obtain particles of PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the microparticles. The washed microparticles were freeze-dried to obtain a microparticle powder.

[0128] To evaluate the content and loading rate of indocyanine green in the prepared microparticles, the concentration of indocyanine green in the microparticle dissolution solution was quantified using an ultraviolet / visible light absorption spectrometer. The content and loading efficiency of indocyanine green in the microparticles were evaluated using the measured concentration of the complex.

[0129] Scanning electron microscopy was performed to analyze the particle morphology, size, and cross-section of the synthesized microparticles. The microparticle powder for surface and cross-section analysis was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface via sputtering for 60 seconds, and then the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the size of 100 random particles in the obtained photograph and averaging it.

[0130] To compare the fluorescence signals between the prepared microparticles and the indocyanine green / human serum albumin complex, an indocyanine green complex solution and a microparticle dispersion were prepared at the same concentration. To compare the fluorescence spectra, 200 μL of each of the prepared solutions and the microparticle dispersion were taken and placed in a 96-well plate, and the fluorescence spectra (λ ex Fluorescence images were analyzed (λ = 730 nm) using a fluorescence imaging device (IVIS Lumina XR) after placing 300 μL of the same solution in a microtube. ex = 780 / 20 nm, λ em =845 / 40 nm).

[0131] In order to evaluate the efficacy of fluorescent labeling of the fluorescent marker microparticles in an animal model, the ICG-HSA solution with a concentration of 30 μM ICG and the microparticles were dispersed in saline for injection containing 0.5% sodium carboxymethyl cellulose (Sigma-Aldrich) and 0.1% Tween 80 (Sigma-Aldrich). 100 μL of the microparticle dispersion was subcutaneously injected into SKH-1 hairless mice using a syringe, and the fluorescent signal over time was photographed (λ = 0.01 μm) using a fluorescent imaging device (IVIS Lumina XR). ex = 780 / 20 nm, λ em =845 / 40 nm).

[0132] In the case of ICG-HSA-Algiante-PLGA (Tween 0.5%) microparticles, in which poloxamer-188, a surfactant that dissolves in the oil phase, was replaced with Tween under the manufacturing conditions of ICG-HSA-Algiante-PLGA (P-188 0.5%) microparticles, the loading rate of indocyanine green in the microparticles was 9.68%, and the content of indocyanine green in 1 mg of microparticles was confirmed to be 81.0 ng.

[0133] As seen in the scanning electron micrograph of Figure 27, the ICG-HSA-Algiante-PLGA (Tween 0.5%) microparticles had a spherical particle morphology (Figure 27(a)), with an average particle diameter of 66.1 ± 26.0 μm, a size suitable for avoiding phagocytosis by macrophages. In addition, as seen in the cross-sectional scanning electron micrograph of the particles (Figure 27(b)), the inside of the microparticles was fractionated into multiple isolated small spheres, and it was confirmed that the microparticles had a structure that inhibited the release of the loaded fluorescent dye, similar to the results of the previous examples.

[0134] The ICG-HSA-Algiante-PLGA (Tween 0.5%) microparticle dispersion showed a fluorescent signal that was 2-fold higher than ICG-HSA and 13-fold higher than ICG-PLGA (without P-188) (Figure 28).

[0135] From the fluorescence image photograph of FIG. 29, it was confirmed that the ICG-HSA-Algiante-PLGA (P-188 0.5%) (FIG. 29-b) microparticle dispersion generated a strong fluorescent signal.

[0136] Figure 30 shows the time-dependent fluorescence images (λ) of ICG-HSA solution (Figure 30-a) and ICG-HSA-Alginate-PLGA (Tween 0.5%) microparticle dispersion (Figure 30-b) subcutaneously injected into SKH-1 hairless mice. ex = 780 / 20 nm, λ emUnlike the case of ICG-HSA injection, the ICG-HSA-Alginate-PLGA (P-188 0.5%) microparticle dispersion did not cause fluorescence bleeding into the surrounding tissue, and it was confirmed that the fluorescent signal was maintained at a high level at the administration site for 30 days.

[0137] The ROI values ​​analyzed from the fluorescent image photographs were plotted in a graph (Figure 31), and it was confirmed that in the case of the ICG-HSA-Alginate-PLGA (Tween 0.5%) microparticle dispersion, 70% of the fluorescence remained after 1 day, and 52% of the fluorescence remained after 30 days. This result shows that even if the surfactant Poloxamer-188 is replaced with another surfactant such as Tween to produce microparticles, it is possible to produce microparticles that can generate high fluorescent signals and fluorescently label lesion sites for a long period of time.

[0138] Example 8: Preparation and analysis of microparticles loaded with indocyanine green / cyclodextrin complex Indocyanine green was complexed with cyclodextrin (mCD) to prepare nanoparticles loaded with the complex, and the fluorescence intensity and utility as a fluorescent marker were analyzed. To prepare indocyanine green / cyclodextrin complex-loaded PLGA microparticles (ICG-mCD-Alginate-PLGA (P-188 0.1%)), a solution of 0.375 mg of indocyanine green (ICG) dissolved in 0.3 mL of ethanol was mixed with a solution of 1.790 mg of methylcyclodextrin (mCD, Sigma-Aldrich) dissolved in 0.6 mL of distilled water and stirred for 6 hours. This was mixed with a solution of 3.6 mg of sodium alginate dissolved in 0.648 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, dissolved at 85 °C while stirring at 600 rpm, and cooled to room temperature to prepare W2 solution. 1.08 g of PLGA and 16.5 g of poloxamer-188 (P-188) were mixed. An oil solution was prepared by adding 14,000 mg of the alginic acid to 15 mL of methylene chloride and dissolving the mixture. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 40 seconds using a water bath ultrasonicator. 0.072 mL of calcium chloride (CaCl2, Sigma-Aldrich) with a concentration of 10.76 mg / mL was added and further ultrasonicated for 40 seconds to prepare a primary emulsion (water-in-oil) in which alginic acid was gelled. The primary emulsion was added to the W2 solution while stirring at 1000 rpm using a mechanical stirrer to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40° C. for 21 hours to remove the methylene chloride solvent. Then, 14,000 mL of the alginic acid was added to the oil solution, and further ultrasonicated for 40 seconds to prepare a primary emulsion (water-in-oil-in-water) in which alginic acid was gelled. The mixture was centrifuged at 400 rpm for 5 minutes to obtain PLGA polymer microparticles loaded with indocyanine green. The supernatant was removed, and the microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0139] The content and loading rate of indocyanine green in the prepared microparticles were analyzed.

[0140] The synthesized microparticles were analyzed by scanning electron microscope to observe the particle morphology, size analysis, and cross-sectional shape. The particle size was calculated by averaging the particle sizes of 100 randomly selected particles in the obtained photograph.

[0141] To compare the fluorescent signals between the microparticles and the indocyanine green / human serum albumin complex, a complex solution and a microparticle dispersion of the same concentration of indocyanine green were prepared. 0.5 mg of indocyanine green powder was dissolved in a mixed solution of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of indocyanine green / human serum albumin complex (ICG-HSA) with a concentration of 30 μM. Using the information on the content of indocyanine green in the PLGA microparticles evaluated by the above quantification, 0.3 mL of distilled water was added to make the concentration of indocyanine green 30 μM to prepare a microparticle dispersion. To compare the fluorescent spectra, 200 μL of each of the solutions and dispersions prepared above were taken and placed in a 96-well plate, and the fluorescent spectra (λ ex Fluorescence images were analyzed (λ = 730 nm) using a fluorescence imaging device (IVIS Lumina XR) after placing 300 μL of the same solution in a microtube. ex = 780 / 20 nm, λ em =845 / 40 nm).

[0142] To evaluate the efficacy of fluorescent labeling of the fluorescent marker microparticles in an animal model, the ICG-HSA solution with a concentration of 30 μM ICG and the microparticles were dispersed in saline for injection containing 0.5% sodium carboxymethyl cellulose (Sigma-Aldrich) and 0.1% Tween 80 (Sigma-Aldrich). 100 μL of the microparticle dispersion was subcutaneously injected into an SKH-1 hairless mouse using a syringe, and the fluorescent signal over time was photographed (λ 0.01 mm) using a fluorescent imaging device (IVIS Lumina XR). ex = 780 / 20 nm, λ em =845 / 40 nm).

[0143] The loading rate of indocyanine green in the ICG-mCD-Alginate-PLGA (P-188 0.1%) microparticles loaded with indocyanine green / cyclodextrin was 11.4%, and the content of indocyanine green in 1 mg of microparticles was confirmed to be 76.3 ng.

[0144] The ICG-mCD-Alginate-PLGA (P-188 0.1%) microparticles were also spherical particles (Figure 32(a)), with an average size of 65.0±26.0μm, suitable for avoiding phagocytosis by macrophages. As can be seen from the cross-sectional photograph of the microparticles in Figure 32(b), the inside of the microparticles is composed of multiple isolated spherical spaces, which indicates that the release of fluorescent dye can be suppressed better than with a microbubble-shaped structure.

[0145] As can be seen from the fluorescence spectrum in Figure 33(a), ICG-mCD shows a fluorescence signal 1.5 times higher than that of ICG, which means that by forming a complex with mCD, the aggregation phenomenon between ICG molecules in aqueous solution can be prevented and the chemical / physical stability of ICG can be increased.

[0146] It was confirmed that the ICG-mCD-Algiante-PLGA (P-188 0.1%) microparticle dispersion prepared using the ICG-mCD complex exhibited a fluorescent signal 4.2 times higher than that of the ICG-PLGA (no P-188) microparticle dispersion.

[0147] Furthermore, from the fluorescence image in Figure 34, it was confirmed that the ICG-mCD-Algiante-PLGA microparticle dispersion (right) generated a high fluorescence signal.

[0148] In Figure 35, it was confirmed that the ICG-mCD-Algiante-PLGA (P-188 0.1%) microparticle dispersion (Figure 35-b) did not show any bleeding phenomenon at the administration site, and the fluorescent signal was maintained for up to 30 days. In the case of ICG-HSA (Figure 35-a), the same behavior as in the previous examples was observed.

[0149] The ROI values ​​analyzed from the fluorescent image were plotted in a graph (Figure 36), and it was confirmed that in the case of the ICG-mCD-Algiante-PLGA (P-188 0.1%) microparticle dispersion, 32% of the fluorescence remained one day after injection, and 29% of the fluorescence remained high even after 30 days. As a result, it was confirmed that the microparticles loaded with indocyanine green / cyclodextrin complex (ICG-mCD-Algiante-PLGA (P-188 0.1%)) were also able to maintain a fluorescent signal for more than 30 days, making them useful as fluorescent markers.

[0150] Example 9: Preparation and analysis of microparticles loaded with Cy7-human serum albumin conjugate A demonstration experiment was conducted to show that it is possible to manufacture microparticles containing other near-infrared fluorescent dyes other than indocyanine green, and that they emit bright fluorescence. For this purpose, sulfo-cyanine 7 carboxylic acid (Cy7), sulfo-cyanine 7.5 carboxylic acid (Cy7.5), Flamma 774 carboxylic acid (Flamma774), Alexa fluor 750 carboxylic acid (Alexa 750), and IRDye 800CW carboxylate (IRDye 800CW) were used as fluorescent dyes to be mounted in the microparticles, and microparticles were manufactured using poly(methyl methacrylate) and polycarbonate (PC) polymers, and their efficacy was evaluated.

[0151] 9-1: Comparison of fluorescent signals depending on the concentration of Cy7 solution and Cy7-HSA complex 0.48 mg of sulfo-cyanine7 carboxylic acid (Cy7, Lumiprobe), a near-infrared fluorescent dye, was dissolved in 1 mL of distilled water and then diluted with distilled water to prepare Cy7 solutions with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. Cy7-human serum albumin (HSA, SK plasma) conjugates were prepared to compare the fluorescence signal with the Cy7 solution. 0.48 mg of Cy7 powder was dissolved in a mixture of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare Cy7-human serum albumin conjugates (Cy7-HSA) with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. For the comparison of fluorescence spectra, 200 μL of each of the prepared solutions was taken and placed in a 96-well plate, and the fluorescence intensity (λ ex = 730 nm, λ em = 780 nm (Cy7), λ emThe emission peak of Cy7 fluorescent dye was measured at 780 nm, but after complexing with HSA, it was also measured at 786 nm.

[0152] As in Figure 37, which compares the fluorescence intensity of Cy7 solutions and Cy7-HSA complex solutions at concentrations of 1 to 100 μM, it was confirmed that the Cy7-HSA solution emitted a higher fluorescence signal than the Cy7 solution at concentrations of 10 μM or higher, and that the Cy7.5-HSA solution emitted a fluorescence signal that was 1.2 times higher than the Cy7.5 solution at a concentration of 30 μM and 1.3 times higher at the maximum measured concentration of 100 μM.

[0153] 9-2: Preparation and analysis of PMMA microparticles loaded with Cy7 and Cy7-HSA complex To prepare PMMA microparticles loaded with Cy7, a near-infrared fluorescent dye, Cy7-PMMA (without P-188), 0.81 mg of Cy7 was dissolved in 1.691 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved while stirring at 600 rpm under the condition of 85 ° C., and cooled to room temperature to prepare W2 solution. 1.217 g of PMMA was added to 16.909 mL of methylene chloride and dissolved to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles carrying Cy7. The supernatant was removed, and the PMMA microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0154] To prepare PMMA microparticles loaded with a near-infrared fluorescent dye Cy7-HSA complex (Cy7-HSA-PMMA (without P-188)), 0.81 mg of Cy7 was dissolved in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved under stirring at 600 rpm at 85 °C, and cooled to room temperature to prepare W2 solution. 1.217 g of PMMA was added to 16.909 mL of methylene chloride and dissolved to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles carrying Cy7-HSA. The supernatant was removed, and the PMMA microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0155] To prepare PMMA microparticles containing 1.0% poloxamer-188 in the primary emulsion phase and loaded with a near-infrared fluorescent dye Cy7-HSA conjugate (Cy7-HSA-PMMA (P-188 1.0%)), 0.81 mg of Cy7 was dissolved in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, dissolved at 85 °C while stirring at 600 rpm, and cooled to room temperature to prepare W2 solution. 1.217 g of PMMA and 186 mg of poloxamer-188 (P-188) were added to 16.909 mL of methylene chloride and dissolved to prepare an oil solution. The prepared W1 solution was added to the oil solution, and ultrasonic treatment was performed for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles loaded with Cy7-HSA. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PMMA microparticles. The washed microparticles were freeze-dried to obtain a microparticle powder.

[0156] To evaluate the content and loading rate of Cy7 in the prepared microparticles, the microparticles were dissolved and the concentration of Cy7 in the solution was quantified using an ultraviolet / visible light absorption spectrometer.

[0157] Scanning electron microscopy was performed to analyze the particle morphology and size of the synthesized microparticles. For cross-sectional analysis of the prepared microparticles, the microparticles were cut with a razor blade. The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface by sputtering for 60 seconds, and then the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0158] To compare the fluorescent signals between the prepared microparticles and the Cy7-human serum albumin complex, a Cy7 complex solution and a microparticle dispersion of the same concentration were prepared. 0.48 mg of Cy7 powder was dissolved in a mixed solution of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of Cy7-human serum albumin complex (Cy7-HSA) with a concentration of 30 μM. Using the information on the Cy7 content in the PMMA microparticles evaluated by the quantification, 0.3 mL of distilled water was added to make the Cy7 concentration 30 μM to prepare a microparticle dispersion. To compare the fluorescent spectra, 200 μL of each of the prepared solutions and microparticle dispersions were taken and placed in a 96-well plate, and the fluorescent spectra (λ ex = 730 nm).

[0159] The loading rate of Cy7 in the Cy7-PMMA (without P-188) microparticles, which were manufactured by loading only Cy7 during the manufacture of PMMA microparticles, was 6.98%, and the Cy7 content in 1 mg of microparticles was 46.5 ng. The loading rates of Cy7 in the Cy7-HSA-PMMA (without P-188) microparticles, which were manufactured by loading Cy7-HSA, and the Cy7-HSA-PMMA (1.0% P-188) microparticles, which were manufactured by adding 1.0% poloxamer-188 to the primary emulsion phase, were 25.8% and 19.1%, and the Cy7 content in 1 mg of microparticles was 162.0 ng and 104.8 ng, respectively, and it was confirmed that the loading rate of Cy7 was higher than that of the Cy7-PMMA (without P-188) microparticles loaded with only Cy7.

[0160] Scanning electron micrographs of Cy7-PMMA (without P-188), Cy7-HSA-PMMA (without P-188), and Cy7-HSA-PMMA (1.0% P-188) microparticles were analyzed, and it was confirmed that each microparticle was a spherical particle with an average particle diameter of 56.7±21.3μm, 53.7±16.1μm, and 59.0±20.0μm, respectively, and had an appropriate size to avoid phagocytosis by macrophages (Figure 38(a, c, d)). In addition, scanning electron microscopy cross-sections of each microparticle (Figure 38(b, d, f)) were observed, and it was confirmed that the PMMA microparticles contained multiple isolated small spherical spaces inside, which could prevent the elution of the fluorescent dye loaded therein, and were therefore very suitable for long-term fluorescent dye labeling.

[0161] In the fluorescence spectrum of the Cy7-PMMA (without P-188) microparticle dispersion in Figure 39, a fluorescence signal 4.2 times lower than that of Cy7-HSA was confirmed, while in the fluorescence spectra of the Cy7-HSA-PMMA (without P-188) and Cy7-HSA-PMMA (1.0% P-188) microparticle dispersions, fluorescence signals 2.5 and 2.8 times higher than that of Cy7-HSA, respectively, and 10 and 12 times higher than that of Cy7-PMMA (without P-188), respectively. From these results, it can be seen that a much higher fluorescence signal can be obtained when the near-infrared fluorescent dye Cy7 is loaded in the form of a complex of Cy7-HSA, rather than when it is loaded alone.

[0162] Example 10: Preparation and analysis of microparticles loaded with Cy7.5-human serum albumin conjugate 10-1: Comparison of fluorescent signals depending on the concentration of Cy7.5 solution and Cy7.5-HSA complex 0.70 mg of sulfo-cyanine7.5 carboxylic acid (Cy7.5, Lumiprobe), a near-infrared fluorescent dye, was dissolved in 1 mL of distilled water and then diluted with distilled water to prepare Cy7.5 solutions with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. Cy7.5-human serum albumin (HSA, SK plasma) complexes for comparing the fluorescence signal with Cy7.5 solutions were prepared by dissolving 0.70 mg of Cy7.5 powder in a mixture of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water and then diluting with distilled water to prepare Cy7.5-human serum albumin complexes (Cy7.5-HSA) with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. For comparison of fluorescence spectra, 200 μL of each of the prepared solutions was taken and placed in a 96-well plate, and the fluorescence spectra (λ ex = 730 nm, λ em = 810 nm (Cy7.5), λ em The fluorescence intensity was measured at 824 nm (Cy7.5-HSA). Cy7.5 fluorescent dye has an emission peak at 810 nm, but after complexing with HSA, it had an emission peak at 824 nm.

[0163] As in Figure 40, which compares the fluorescence intensity of Cy7.5 solutions and Cy7.5-HSA complex solutions at concentrations of 1 to 100 μM, it was confirmed that the Cy7.5-HSA solution generated a higher fluorescence signal than the Cy7.5 solution at concentrations of 10 μM or higher, and that the Cy7.5-HSA solution generated a fluorescence signal that was 1.1 times higher than the Cy7.5 solution at a concentration of 30 μM and 1.2 times higher at a concentration of 100 μM, which was the maximum concentration measured.

[0164] 10-2: Preparation and analysis of PMMA microparticles loaded with Cy7.5 and Cy7.5-HSA complex To prepare PMMA particles loaded with only the near-infrared fluorescent dye Cy7.5 (Cy7.5-PMMA (without P-188)), 1.18 mg of Cy7.5 was dissolved in 1.691 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved while stirring at 600 rpm under the condition of 85 ° C., and cooled to room temperature to prepare W2 solution. 1.217 g of PMMA was added and dissolved in 16.909 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). While stirring the prepared W2 solution at 1000 rpm using a mechanical stirrer, the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles carrying Cy7.5. The supernatant was removed, and the PMMA microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0165] Cy7.5-HSA-PMMA (without P-188), which is PMMA particles loaded with a near-infrared fluorescent dye Cy7.5-HSA complex, was prepared. W1 solution was prepared by dissolving 1.18 mg of Cy7.5 in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water. W2 solution was prepared by adding 3.6 g of polyvinyl alcohol to 180 mL of distilled water, dissolving it under stirring at 600 rpm at 85 ° C, and cooling it to room temperature. An oil solution was prepared by adding 1.217 g of PMMA to 16.909 mL of methylene chloride and dissolving it. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles loaded with Cy7.5-HSA. The supernatant was removed, and the PMMA microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0166] Cy7.5-HSA-PMMA (P-188 1.0%), PMMA particles containing poloxamer-188 at a concentration of 1.0% and loaded with a near-infrared fluorescent dye Cy7.5-HSA complex, was prepared. W1 solution was prepared by dissolving 1.18 mg of Cy7.5 in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water. W2 solution was prepared by adding 3.6 g of polyvinyl alcohol to 180 mL of distilled water, dissolving it under stirring at 600 rpm at 85 °C, and cooling it to room temperature. PMMA 1.217 g and 186 mg of poloxamer-188 (P-188) were added to 16.909 mL of methylene chloride and dissolved to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles loaded with Cy7.5-HSA. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PMMA microparticles. The washed microparticles were freeze-dried to obtain a microparticle powder.

[0167] To evaluate the content and loading rate of Cy7.5 in the prepared microparticles, the microparticles were dissolved and the concentration of Cy7.5 in the solution was quantified using an ultraviolet / visible light absorption analyzer.

[0168] Scanning electron microscopy was performed to analyze the particle morphology and size of the synthesized microparticles. For cross-sectional analysis of the prepared microparticles, the microparticles were cut with a razor blade. The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface by sputtering for 60 seconds, and then the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0169] To compare the fluorescence signals between the prepared microparticles and the Cy7.5-human serum albumin complex, a Cy7.5 complex solution and a microparticle dispersion of the same concentration were prepared. 0.70 mg of Cy7.5 powder was dissolved in a mixed solution of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of Cy7.5-human serum albumin complex (Cy7-HSA) with a concentration of 30 μM. Using the information on the content of Cy7.5 in the PMMA microparticles evaluated by the quantification, a microparticle dispersion was prepared by adding 0.3 mL of distilled water so that the concentration of Cy7.5 was 30 μM. To compare the fluorescence spectra, 200 μL of each of the prepared solutions and microparticle dispersions were taken and placed in a 96-well plate, and the fluorescence spectra (λ ex = 730 nm).

[0170] The loading rate of Cy7.5 in the microparticles of Cy7.5-PMMA (without P-188) prepared by loading Cy7.5 during the preparation of PMMA microparticles was 4.10%, and the content of Cy7.5 in 1 mg of microparticles was 39.8 ng. The loading rates of Cy7.5 in the microparticles of Cy7.5-HSA-PMMA (without P-188) prepared by loading Cy7.5-HSA and Cy7.5-HSA-PMMA (1.0% P-188) prepared by adding 1.0% poloxamer-188 to the primary emulsion phase were 14.0% and 15.6%, and the content of Cy7.5 in 1 mg of microparticles was 128.7 ng and 124.7 ng, respectively, confirming that the loading rate of Cy7.5 was higher than that of Cy7.5-PMMA (without P-188) microparticles loaded with Cy7.5 alone.

[0171] Scanning electron micrographs of Cy7.5-PMMA (without P-188), Cy7.5-HSA-PMMA (without P-188), and Cy7.5-HSA-PMMA (1.0% P-188) microparticles were analyzed, and it was confirmed that each microparticle was a spherical particle with an average particle diameter of 57.9±18.4 μm, 58.0±16.0 μm, and 65.9±24.4 μm, respectively, and had an appropriate size to avoid phagocytosis by macrophages (Figure 41(a, c, e)). In addition, scanning electron microscopy cross-sections of each microparticle (Figure 41(b, d, f)) were evaluated, and it was confirmed that the PMMA microparticles contain multiple isolated small spherical spaces inside, which can prevent the elution of the fluorescent dye loaded therein, and are therefore highly suitable for long-term fluorescent dye labeling.

[0172] In the fluorescence spectrum of the Cy7.5-PMMA (without P-188) microparticle dispersion in Figure 42, a fluorescence signal 5.0 times lower than that of Cy7.5-HSA was confirmed, while in the fluorescence spectra of the Cy7.5-HSA-PMMA (without P-188) and Cy7.5-HSA-PMMA (1.0% P-188) microparticle dispersions, the fluorescence signals were 1.3 and 1.6 times higher than that of Cy7.5-HAS, respectively, and 6.4 and 8.2 times higher than that of Cy7.5-PMMA (without P-188). From these results, it can be seen that a very high fluorescence signal can be obtained when the near-infrared fluorescent dye Cy7.5 is loaded in the form of a complex of Cy7.5-HSA, rather than when it is loaded alone.

[0173] 10-3: Preparation and analysis of Cy7.5 and Cy7.5-HSA loaded polycarbonate microparticles Cy7.5-PC (without P-188), which is a polycarbonate (PC) microparticle loaded with the near-infrared fluorescent dye Cy7.5, was prepared. W1 solution was prepared by dissolving 1.18 mg of Cy7.5 in 1.691 mL of distilled water. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved under stirring at 600 rpm at 85°C, and cooled to room temperature to prepare W2 solution. 1.217 g of PC was added to 16.909 mL of methylene chloride and dissolved to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain the particles of PC polymer microparticles carrying Cy7.5. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PC microparticles. The washed microparticle particles were freeze-dried to obtain a microparticle powder.

[0174] Cy7.5-HSA-PC (without P-188), which is PC microparticles loaded with Cy7.5-HSA complex, was prepared. W1 solution was prepared by dissolving 1.18 mg of Cy7.5 in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water. W2 solution was prepared by adding 3.6 g of polyvinyl alcohol to 180 mL of distilled water, dissolving it under stirring at 600 rpm at 85 ° C, and cooling it to room temperature. PC was added to 16.909 mL of methylene chloride and dissolved therein to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain the particles of PC polymer microparticles loaded with Cy7.5-HSA. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PC microparticles. The washed microparticle particles were freeze-dried to obtain a microparticle powder.

[0175] To evaluate the content and loading rate of Cy7.5 in the prepared microparticles, the microparticles were dissolved, and the concentration of Cy7.5 in the solution was quantified using an ultraviolet / visible light absorption spectrometer.

[0176] Scanning electron microscopy was performed to analyze the particle morphology and size of the synthesized microparticles. For cross-sectional analysis of the prepared microparticles, the microparticles were cut with a razor blade. The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface by sputtering for 60 seconds, and then the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0177] In order to compare the fluorescent signals between the prepared microparticles and the Cy7.5-human serum albumin complex, a Cy7.5 complex solution and a microparticle dispersion of the same concentration were prepared. 0.70 mg of Cy7.5 powder was dissolved in a mixed solution of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of Cy7.5-human serum albumin complex (Cy7-HSA) with a concentration of 30 μM. Using the information on the content of Cy7.5 in the PC microparticles evaluated by the above quantification, 0.3 mL of distilled water was added to make the concentration of Cy7.5 30 μM to prepare a microparticle dispersion. In order to compare the fluorescent spectra, 200 μL of each of the prepared solutions and microparticle dispersions were taken and placed in a 96-well plate, and the fluorescent spectra (λ ex = 730 nm).

[0178] The loading rate of Cy7.5 in the Cy7.5-PMMA (without P-188) microparticles, which were prepared by loading Cy7.5 during the preparation of PMMA microparticles, was 2.08%, and the content of Cy7.5 in 1 mg of microparticles was confirmed to be 20.2 ng. The loading rate of Cy7.5 in the Cy7.5-HSA-PMMA (1.0% P-188) microparticles, which were prepared by loading Cy7.5-HSA and adding 1.0% poloxamer-188 based on the primary emulsion phase, was 11.8%, and the content of Cy7.5 in 1 mg of microparticles was 108.6 ng, confirming that the loading rate was higher than that of Cy7.5-PMMA (without P-188) microparticles.

[0179] Analysis of scanning electron micrographs of Cy7.5-PMMA (without P-188) and Cy7.5-HSA-PMMA (without P-188) microparticles confirmed that each microparticle was a spherical particle with an average particle diameter of 58.3±19.0μm and 55.2±19.5μm, which is an appropriate size to avoid phagocytosis by macrophages (Figure 43(a, c)). In addition, by observing the scanning electron microscopy cross-sections of each microparticle (Figure 43(b, d)), it was confirmed that the PMMA microparticles contain multiple isolated small spherical spaces inside, which can prevent the elution of the fluorescent dye loaded, making them a very suitable form for long-term fluorescent dye labeling.

[0180] In the fluorescence spectrum of the Cy7.5-HSA-PC (without P-188) microparticle dispersion in Figure 44, a fluorescent signal 2.2 times higher than that of Cy7.5-PC (without P-188) was confirmed. From this result, it can be seen that a much higher fluorescent signal can be obtained when the near-infrared fluorescent dye Cy7.5 is loaded in the form of a Cy7.5-HSA complex onto microparticles based on PC polymers, compared to when it is loaded alone.

[0181] Example 11: Preparation and analysis of microparticles loaded with Flamm774-human serum albumin conjugates 11-1: Comparison of fluorescent signals depending on the concentration of Flamma774 solution and Flamma774-HSA complex 0.60 mg of Flamma774 carboxylic acid (Flamma774, Bioacts), a near-infrared fluorescent dye, was dissolved in 1 mL of distilled water, and then diluted with distilled water to prepare Flamma774 solutions with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. To compare the fluorescent signal with the Flamma774 solution, Flamma774-human serum albumin (HSA, SK plasma) complex was prepared by dissolving 0.60 mg of Flamma774 powder in a mixture of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluting with distilled water to prepare Flamma774-human serum albumin complexes (Flamma774-HSA) with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. For comparison of fluorescence spectra, 200 μL of each of the prepared solutions was taken and placed in a 96-well plate, and the fluorescence spectra (λ ex = 730 nm, λ em = 812 nm (Flamma 774), λ em The Flamma774 fluorescent dye has an emission peak at 812 nm, but after complexing with HSA, it also had an emission peak at 818 nm.

[0182] As in Figure 45, which compares the fluorescence intensities of Flamma774 solutions and Flamma774-HSA complex solutions at concentrations of 1 to 100 μM, it was confirmed that the Flamma774-HSA solution emitted higher fluorescence signals than the Flamma774 solution over the entire range of concentrations, and that the Flamma774-HSA solution emitted fluorescence signals 1.3 times higher than the Flamma774 solution at a concentration of 30 μM and 1.3 times higher at the maximum measured concentration of 100 μM.

[0183] 11-2: Preparation and analysis of PMMA microparticles loaded with Flamma774 and Flamma774-HSA complex Flamma774-PMMA (without P-188), which is PMMA microparticles loaded with near-infrared fluorescent dye Flamma774, was prepared. 1.01 mg of Flamma774 was dissolved in 1.691 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved while stirring at 600 rpm under the condition of 85 ° C., and cooled to room temperature to prepare W2 solution. 1.217 g of PMMA was added to 16.909 mL of methylene chloride and dissolved to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticle particles equipped with Flamma774. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PMMA microparticles. The washed microparticle particles were freeze-dried to obtain microparticle powder.

[0184] Flamma774-HSA-PMMA (without P-188), which is PMMA microparticles loaded with Flamma774-HSA complex, was prepared. 1.01 mg of Flamma774 was dissolved in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved while stirring at 600 rpm under the condition of 85 ° C., and cooled to room temperature to prepare W2 solution. 1.217 g of PMMA was added and dissolved in 16.909 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles loaded with Flamma774-HSA. The supernatant was removed, and the PMMA microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0185] Flamma774-HSA-PMMA (P-188 1.0%), which is PMMA microparticles loaded with near-infrared fluorescent dye Flamma774-HSA complex containing 1.0% poloxamer-188 in the primary emulsion phase, was prepared. W1 solution was prepared by dissolving 1.01 mg of Flamma774 in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water. W2 solution was prepared by adding 3.6 g of polyvinyl alcohol to 180 mL of distilled water, dissolving it under stirring at 600 rpm at 85 °C, and cooling it to room temperature. An oil solution was prepared by adding 1.217 g of PMMA and 186 mg of poloxamer-188 (P-188) to 16.909 mL of methylene chloride and dissolving it. The prepared W1 solution was added to the oil solution, and ultrasonic treatment was performed for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticle particles loaded with Flamma774-HSA. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PMMA microparticles. The washed microparticles were freeze-dried to obtain a microparticle powder.

[0186] To evaluate the content and loading rate of Flmma774 in the prepared microparticles, the microparticles were dissolved, and the concentration of Flmma774 in the solution was quantified using an ultraviolet / visible light absorption spectrometer.

[0187] Scanning electron microscopy was performed to analyze the particle morphology and size of the synthesized microparticles. For cross-sectional analysis of the prepared microparticles, the microparticles were cut with a razor blade. The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface by sputtering for 60 seconds, and then the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0188] To compare the fluorescence signals between the prepared microparticles and the Flmma774-human serum albumin complex, a complex solution and a microparticle dispersion of Flmma774 with the same concentration were prepared. 0.60 mg of Flmma774 powder was dissolved in a mixture of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of Flmma774-human serum albumin complex (Flmma774-HSA) with a concentration of 30 μM. Using the information on the content of Flmma774 in the PMMA microparticles evaluated by the above quantification, a microparticle dispersion was prepared by adding 0.3 mL of distilled water so that the concentration of Flmma774 was 30 μM. To compare the fluorescence spectra, 200 μL of each of the prepared solutions and microparticle dispersions were taken and placed in a 96-well plate, and the fluorescence spectra (λ ex = 730 nm).

[0189] The loading rate of Flamma774 in Flamma774-PMMA (without P-188) microparticles, which were prepared by adding Flamma774 during the preparation of PMMA microparticles, was 5.08%, and the content of Flamma774 in 1 mg of microparticles was 42.3 ng. The loading rate of Flamma774 in Flamma774-HSA-PMMA (without P-188) microparticles, which were prepared by adding 1.0% poloxamer-188 to the primary emulsion phase, was 23.3% and 21.6%, and the content of Flamma774 in 1 mg of microparticles was 183.0 ng and 148.6 ng, respectively, indicating that the loading rate was higher than that of Flamma774-PMMA (without P-188) microparticles loaded with Flamma774 alone.

[0190] Scanning electron micrographs of Flamma774-PMMA (without P-188), Flamma774-HSA-PMMA (without P-188), and Flamma774-HSA-PMMA (1.0% P-188) microparticles were analyzed, and it was confirmed that each microparticle was a spherical particle with an average particle diameter of 56.8±19.2 μm, 62.5±19.3 μm, and 55.8±19.3 μm, respectively, and had an appropriate size to avoid phagocytosis by macrophages (Figure 46(a, c, e)). In addition, scanning electron microscopy cross-sections of each microparticle (Figure 46(b, d, f)) were analyzed, and it was confirmed that the PMMA microparticles contained multiple isolated small spherical spaces inside, which could prevent the elution of the fluorescent dye loaded therein, and were therefore very suitable for long-term fluorescent dye labeling.

[0191] In the fluorescence spectrum of the Flamma774-PMMA (without P-188) microparticle dispersion in Figure 47, a fluorescence signal 4.5 times lower than that of Flamma774-HSA was confirmed, and in the fluorescence spectra of the Flamma774-HSA-PMMA (without P-188) and Flamma774-HSA-PMMA (1.0% P-188) microparticle dispersions, a fluorescence signal 1.4 times and 2.3 times higher than that of Flamma774-HSA, respectively, and a fluorescence signal 6.2 times and 10.4 times higher than that of Flamma774-PMMA (without P-188), respectively. From these results, it can be seen that a very high fluorescence signal can be obtained when the near-infrared fluorescent dye Flamma774 is loaded in the form of a complex of Flamma774-HSA, rather than when it is loaded alone.

[0192] Example 12: Preparation and analysis of microparticles loaded with Alexa750-human serum albumin conjugates 12-1: Comparison of fluorescent signals depending on the concentration of Alexa750 solution and Alexa750-HSA complex Alexa fluor, a near-infrared fluorescent dye TM0.77 mg of 750 carboxylic acid, tris(triethylammonium)salt (Alexa750, Thermo Fisher Scientific) was dissolved in 1 mL of distilled water, and then diluted with distilled water to prepare Alexa750 solutions with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. To compare the fluorescent signal with the Alexa750 solution, 0.77 mg of Alexa750 powder was dissolved in a mixture of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare Alexa750-human serum albumin complexes (Alexa750-HSA) with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. For comparison of fluorescence spectra, 200 μL of each of the prepared solutions was taken and placed in a 96-well plate, and the fluorescence spectra (λ ex = 730 nm, λ em = 776 nm).

[0193] As in Figure 48, which compares the fluorescence intensities of Alexa750 solutions and Alexa750-HSA complex solutions at concentrations of 1 to 100 μM, it was confirmed that the Alexa750-HSA solution generated a higher fluorescence signal than the Alexa750 solution over the entire range of concentrations, and that the Alexa750-HSA solution generated a fluorescence signal that was 1.1 times higher than the Alexa750 solution at a concentration of 30 μM and 1.1 times higher at the maximum measured concentration of 100 μM.

[0194] 12-2: Preparation and analysis of PMMA microparticles loaded with Alexa750 and Alexa750-HSA complex Alexa750-PMMA (without P-188), which is PMMA microparticles loaded with near-infrared fluorescent dye Alexa750, was prepared. 1.31 mg of Alexa750 was dissolved in 1.691 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved while stirring at 600 rpm under the condition of 85 ° C., and cooled to room temperature to prepare W2 solution. 1.217 g of PMMA was added and dissolved in 16.909 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles loaded with Alexa 750. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PMMA microparticles. The washed microparticles were freeze-dried to obtain microparticle powder.

[0195] Alexa750-HSA-PMMA (without P-188), which is PMMA microparticles loaded with a near-infrared fluorescent dye Alexa750-HSA complex, was prepared. 1.31 mg of Alexa750 was dissolved in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water to prepare W1 solution. 3.6 g of polyvinyl alcohol was added to 180 mL of distilled water, and dissolved while stirring at 600 rpm under the condition of 85 ° C., and cooled to room temperature to prepare W2 solution. 1.217 g of PMMA was added and dissolved in 16.909 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles loaded with Alexa750-HSA. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PMMA microparticles. The washed microparticles were freeze-dried to obtain microparticle powder.

[0196] Alexa750-HSA-PMMA (P-188 1.0%), which is PMMA microparticles loaded with near-infrared fluorescent dye Alexa750-HSA complex containing 1.0% poloxamer-188 in the primary emulsion phase, was prepared. W1 solution was prepared by dissolving 1.31 mg of Alexa750 in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water. W2 solution was prepared by adding 3.6 g of polyvinyl alcohol to 180 mL of distilled water, dissolving it under stirring at 600 rpm at 85 °C, and cooling it to room temperature. PMMA 1.217 g and 186 mg of poloxamer-188 (P-188) were added and dissolved in 16.909 mL of methylene chloride to prepare an oil solution. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain particles of PMMA polymer microparticles loaded with Alexa750-HSA. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PMMA microparticles. The washed microparticles were freeze-dried to obtain a microparticle powder.

[0197] To evaluate the content and loading rate of Alexa 750 in the prepared microparticles, the microparticles were dissolved and the concentration of Alexa 750 in the solution was quantified using an ultraviolet / visible light absorption spectrometer.

[0198] Scanning electron microscopy was performed to analyze the particle morphology and size of the synthesized microparticles. For cross-sectional analysis of the prepared microparticles, the microparticles were cut with a razor blade. The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface by sputtering for 60 seconds, and then the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0199] To compare the fluorescent signals between the microparticles and the Alexa750-human serum albumin complex, a complex solution and a microparticle dispersion of the same concentration of Alexa750 were prepared. 0.77 mg of Alexa750 powder was dissolved in a mixed solution of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, and then diluted with distilled water to prepare 0.3 mL of Alexa750-human serum albumin complex (Alexa750-HSA) with a concentration of 30 μM. The content of Alexa750 in the PMMA microparticles evaluated by the above quantification was added to 0.3 mL of distilled water so that the concentration of Alexa750 was 30 μM, and a microparticle dispersion was prepared. To compare the fluorescent spectra, 200 μL of each of the solutions and microparticle dispersions prepared above were taken and placed in a 96-well plate, and the fluorescent spectra (λ ex = 730 nm).

[0200] The loading rate of Alexa750 in the Alexa750-PMMA (without P-188) microparticles, which were prepared by loading Alexa750 during the preparation of PMMA microparticles, was 14.1%, and the content of Alexa750 in 1 mg of microparticles was confirmed to be 151.8 ng. The loading rate of Alexa750 in the Alexa750-HSA-PMMA (without P-188) microparticles, which were prepared by loading Alexa750-HSA, was confirmed to be 9.61%, and the content of Alexa750 in 1 mg of microparticles was confirmed to be 97.7 ng. The loading rate of Alexa750 in the Alexa750-HSA-PMMA (1.0% P-188) microparticles, which were prepared by adding 1.0% poloxamer-188 based on the primary emulsion phase, was confirmed to be 21.2%, and the content of Alexa750 in 1 mg of microparticles was 188.1 ng, indicating that the microparticles were loaded with a higher content of Alexa750 than the other two microparticles.

[0201] The Alexa750-PMMA (without P-188), Alexa750-HSA-PMMA (without P-188), and Alexa750-HSA-PMMA (1.0% P-188) microparticles were confirmed to have an appropriate size to avoid macrophage phagocytosis as spherical particles with average particle diameters of 53.0 ± 15.8 μm, 54.6 ± 20.3 μm, and 57.7 ± 19.6 μm, respectively. As a result of evaluating the scanning electron microscope cross-sections of each microparticle (Figure 49), it was confirmed that the interior of the PMMA microparticles contains multiple isolated small spherical spaces, which can prevent the elution of the loaded fluorescent dye, and is a morphology that is very suitable for long-term fluorescent dye labeling.

[0202] In the fluorescence spectrum of the Alexa750-PMMA (without P-188) microparticle dispersion in Figure 50, a fluorescent signal 6.5 times lower than that of Alexa750-HSA was confirmed, and in the fluorescence spectra of the Alexa750-HSA-PMMA (without P-188) and Alexa750-HSA -PMMA (1.0% P-188) microparticle dispersions, fluorescent signals 2.0 and 1.9 times higher than that of Alexa750-HAS, respectively, and 13 and 12 times higher than that of Alexa750-PMMA (without P-188). From these results, it can be seen that a very high fluorescent signal can be obtained when the near-infrared fluorescent dye Alexa750 is loaded in the form of a complex of Alexa750-HSA, rather than when it is loaded alone.

[0203] Example 13: Preparation and analysis of microparticles loaded with IRDye 800CW-human serum albumin conjugate 13-1: Comparison of fluorescence signals depending on the concentration of IRDye 800CW solution and IRDye 800CW-HSA conjugate 0.70 mg of the near-infrared fluorescent dye IRDye® 800CW carboxylate (IRDye 800CW, LI-COR, Inc.) was dissolved in 1 mL of distilled water and then diluted with distilled water to prepare Alexa 750 solutions with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. To compare the fluorescence signal with the IRDye 800CW solution, the IRDye 800CW-human serum albumin (HSA, SK plasma) complex was prepared by dissolving 0.70 mg of IRDye 800CW powder in a mixture of 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water, followed by dilution with distilled water to prepare IRDye 800CW / human serum albumin complexes (IRDye 800CW-HSA) with concentrations of 100, 70, 50, 40, 30, 20, 10, 5, 4, 3, 2, and 1 μM. To compare the fluorescence spectra, 200 μL of each of the solutions prepared above was taken and placed in a 96-well plate, and the fluorescence spectra (λex = 730 nm, λ em = 806 nm (IRDye 800CW), λ em The IRDye 800CW fluorescent dye exhibits an emission peak at 806 nm, but after complexing with HSA, it exhibits an emission peak at 810 nm.

[0204] As in FIG. 51 which compares the fluorescence intensities of IRDye 800CW solutions and IRDye 800CW-HSA conjugate solutions at concentrations of 1 to 100 μM, it was confirmed that the IRDye 800CW-HSA solution emitted a higher fluorescence signal than the IRDye 800CW solution at concentrations of 3 μM or higher, and that the IRDye 800CW-HSA solution emitted a fluorescence signal 1.1 times higher than the IRDye 800CW solution at a concentration of 30 μM and 1.1 times higher at the maximum measured concentration of 100 μM.

[0205] 13-2: Preparation and analysis of PMMA microparticles loaded with IRDye 800CW and IRDye 800CW-HSA composite IRDye 800CW-PMMA (without P-188), which is PMMA microparticles loaded with the near-infrared fluorescent dye IRDye 800CW, was prepared. W1 solution was prepared by dissolving 1.19 mg of IRDye 800CW in 1.691 mL of distilled water. W2 solution was prepared by adding 3.6 g of polyvinyl alcohol to 180 mL of distilled water, dissolving it under stirring at 600 rpm at 85°C, and cooling it to room temperature. An oil solution was prepared by adding 1.217 g of PMMA to 16.909 mL of methylene chloride and dissolving it. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). While stirring the prepared W2 solution at 1000 rpm using a mechanical stirrer, the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles equipped with IRDye 800CW. The supernatant was removed, and the PMMA microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0206] IRDye 800CW-HSA-PMMA (without P-188), which is PMMA microparticles loaded with a near-infrared fluorescent dye IRDye 800CW-HSA complex, was prepared. W1 solution was prepared by dissolving 1.19 mg of IRDye 800CW in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water. W2 solution was prepared by adding 3.6 g of polyvinyl alcohol to 180 mL of distilled water, dissolving it under stirring at 600 rpm at 85 °C, and cooling it to room temperature. An oil solution was prepared by adding 1.217 g of PMMA to 16.909 mL of methylene chloride and dissolving it. The prepared W1 solution was added to the oil solution, and then ultrasonicated for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm for 21 hours using a magnetic stirrer at a temperature condition of 40°C to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticles equipped with IRDye 800CW-HSA. The supernatant was removed, and the PMMA microparticles were washed by adding distilled water, redispersing, and centrifuging three times. The washed microparticles were freeze-dried to obtain microparticle powder.

[0207] IRDye 800CW-HSA-PMMA (P-188 1.0%), PMMA microparticles loaded with near-infrared fluorescent dye IRDye 800CW-HSA complex containing 1.0% poloxamer-188 in the primary emulsion phase, was prepared. W1 solution was prepared by dissolving 1.19 mg of IRDye 800CW in 0.363 mL of human serum albumin (HSA) (20% concentration, 72.553 mg) and 1.328 mL of distilled water. W2 solution was prepared by adding 3.6 g of polyvinyl alcohol to 180 mL of distilled water, dissolving it under stirring at 600 rpm at 85 °C, and cooling it to room temperature. An oil solution was prepared by adding and dissolving 1.217 g of PMMA and 186 mg of poloxamer-188 (P-188) in 16.909 mL of methylene chloride. The prepared W1 solution was added to the oil solution, and ultrasonic treatment was performed for 3 minutes (1 minute ultrasonic treatment + 30 seconds pause repeated) using a probe-type ultrasonic device to prepare a primary emulsion (water-in-oil). The prepared W2 solution was stirred at 1000 rpm using a mechanical stirrer, and the prepared primary emulsion solution was added at a rate of 10 mL / min using a syringe pump to prepare a secondary emulsion (water-in-oil-in-water). The prepared emulsion was stirred at 1000 rpm for 10 minutes, and then stirred at 280 rpm using a magnetic stirrer at a temperature condition of 40°C for 21 hours to remove the methylene chloride solvent. Then, it was centrifuged at 14,000 rpm for 5 minutes to obtain PMMA polymer microparticle particles equipped with IRDye 800CW-HSA. The supernatant was removed, and the process of adding distilled water, redispersing, and centrifuging was repeated three times to wash the PMMA microparticles. The washed microparticles were freeze-dried to obtain a microparticle powder.

[0208] To evaluate the content and loading rate of IRDye 800CW in the prepared microparticles, the microparticles were dissolved and the concentration of IRDye 800CW in the solution was quantified using an ultraviolet / visible light absorption analyzer.

[0209] Scanning electron microscopy was performed to analyze the particle morphology and size of the synthesized microparticles. For cross-sectional analysis of the prepared microparticles, the microparticles were cut with a razor blade. The microparticle powder was attached to a carbon tape attached to a scanning electron microscope sample holder, and Pt / Pd was coated on the surface by sputtering for 60 seconds, and then the scanning electron microscope photograph was analyzed at an accelerating voltage of 5 kV. The particle size was calculated by measuring the particle size of 100 random particles in the obtained photograph and averaging it.

[0210] To compare the fluorescent signals of the prepared microparticles and IRDye 800CW-human serum albumin conjugate, Alexa 750 conjugate solution and microparticle dispersion of the same concentration were prepared. 0.70 mg of IRDye 800CW powder was dissolved in 0.214 mL of human serum albumin solution (20% concentration) and 0.786 mL of distilled water mixed solution, and then diluted with distilled water to prepare 0.3 mL of IRDye 800CW-human serum albumin conjugate (IRDye 800CW-HSA) with a concentration of 30 μM. The content of IRDye 800CW in the PMMA microparticles evaluated by the above quantification was added to 0.3 mL of distilled water so that the concentration of IRDye 800CW was 30 μM, and a microparticle dispersion was prepared. To compare the fluorescent spectra, 200 μL of the prepared solution and microparticle dispersion were each taken and placed in a 96-well plate, and the fluorescent spectra (λ ex = 730 nm).

[0211] The loading rate of IRDye 800CW in the IRDye 800CW-PMMA (without P-188) microparticles, which were manufactured by incorporating IRDye 800CW during the production of PMMA microparticles, was 10.7%, and the content of IRDye 800CW in 1 mg of microparticles was confirmed to be 104.4 ng. The loading rates of IRDye 800CW in IRDye 800CW-HSA-PMMA (without P-188) microparticles prepared by adding IRDye 800CW-HSA and IRDye 800CW-HSA-PMMA (1.0% P-188) microparticles prepared by adding 1.0% poloxamer-188 based on the primary emulsion phase were 19.5% and 19.0%, respectively, and the IRDye 800CW content per 1 mg of microparticles was 179.6 ng and 152.8 ng, respectively, confirming that the loading rate of IRDye 800CW was higher than that of IRDye 800CW-PMMA (without P-188) microparticles.

[0212] Scanning electron micrographs of IRDye 800CW-PMMA (without P-188), IRDye 800CW-HSA-PMMA (without P-188), and IRDye 800CW-HSA-PMMA (1.0% P-188) microparticles were analyzed, and it was confirmed that each microparticle was a spherical particle with an average particle diameter of 55.8±19.7 μm, 66.6±13.8 μm, and 59.8±17.3 μm, respectively, which is an appropriate size to avoid phagocytosis by macrophages (Figure 52(a, c, e)). In addition, scanning electron micrographs of each microparticle (Figure 52(b, d, f)) were analyzed, and it was confirmed that the PMMA microparticles have multiple isolated small spherical spaces inside, which can prevent the elution of the fluorescent dye loaded, and are very suitable for long-term fluorescent dye labeling.

[0213] In the fluorescence spectrum of the IRDye 800CW-PMMA (without P-188) microparticle dispersion in Figure 53, a fluorescence signal 6.2 times lower than that of IRDye 800CW-HSA was observed, while in the fluorescence spectra of the IRDye 800CW-HSA-PMMA (without P-188) and IRDye 800CW-HSA-PMMA (1.0% P-188) microparticle dispersions, the fluorescence signals were 4.0 and 3.9 times higher than that of IRDye 800CW-HSA, respectively, and 25 and 24 times higher than that of IRDye 800CW-PMMA (without P-188), respectively. From these results, it can be seen that a much higher fluorescence signal can be obtained when the near-infrared fluorescent dye IRDye 800CW is loaded in the form of a complex with IRDye 800CW-HSA than when it is loaded alone.

[0214] Example 14: Preparation of a dispersion composition of PLGA microparticles and preparation and analysis of a marker in pellet form containing the microparticles As a representative example of biodegradable polymer, microparticles prepared using PLGA polymer were dispersed in various other surfactants or biocompatible polymeric substances to prepare dispersion aqueous solution compositions for injection administration. The microparticles used in this example were ICG-HSA-PLGA (P-188 0.5%). To disperse the microparticles, a solution of 0.5% sodium methylcellulose (Sigma-Aldrich) / 0.1% Tween 80 (Sigma-Aldrich) was dissolved in saline for injection, and a solution of 1% sodium alginate (Kimica), 1% sodium hyaluronate (MW 1M) (Lifecore biomedical), 2% soidum methylcellulose (Sigma-Aldrich), 2% poly(vinyl alcohol) (Sigma-Aldrich), 0.1% collagen (collagen from calf skin, Sigma-Aldrich), 5% gelatin (gelatin from porcine, Sigma-Aldrich), 10% Tween 80 (Sigma-Aldrich), 40% poloxamer 188 (BASF), and 5% polyvinyl pyrrolidone (Sigma-Aldrich) was prepared. 0.5%), the microparticles were dispersed in each solution so that the concentration of indocyanine green in the microparticles was 30 μM.

[0215] To prepare a solid-form lesion labeling preparation, a marker in the form of a dried pellet was prepared by transferring microparticles dispersed in 1% sodium hyaluronate and 5% gelatin aqueous solution into a cylindrical frame, rapidly cooling with liquid nitrogen, and freeze-drying to prepare a fluorescent marker in the form of a solid pellet.

[0216] The results of preparing compositions in which the microparticles were dispersed in various other surfactants and biocompatible polymeric substances are shown in Figure 54. It was confirmed that the ICG-HSA-PLGA (P-188 0.5%) microparticles were uniformly dispersed in all the composition solutions used.

[0217] Furthermore, FIG. 55 confirms that it is possible to produce a fluorescent marker in the form of a solid pellet using microparticles dispersed in a 1% sodium hyaluronate and 5% gelatin solution.

[0218] Example 15: Preparation of a dispersion composition of PMMA microparticles and preparation and analysis of a pellet-shaped marker containing the microparticles As a representative example of a non-biodegradable polymer, PMMA polymer was used to prepare microparticles, which were then dispersed in various other surfactants or biocompatible polymeric substances to prepare aqueous dispersion compositions for injection. The microparticles used in this example were ICG-HSA-PMMA (P-188 1.0%) microparticles.

[0219] To disperse the microparticles, a solution of 0.5% sodium methylcellulose (Sigma-Aldrich) / 0.1% Tween 80 (Sigma-Aldrich) dissolved in injectable saline, 1% sodium alginate, 1% sodium hyaluronate, 2% sodium methylcellulose, 2% poly(vinyl alcohol), 0.1% collagen, 5% gelatin, 10% Tween 80, 40% poloxamer 188, and 5% polyvinyl pyrrolidone was prepared, and the microparticles were dispersed in each solution so that the concentration of indocyanine green in the ICG-HSA-PMMA (P-188 1.0%) microparticles was 30 μM.

[0220] To prepare a solid-form lesion labeling preparation, a marker in the form of a dried pellet was prepared by transferring the microparticles dispersed in an aqueous solution of 1% sodium alginate, 1% sodium hyaluronate, 2% sodium methylcellulose, 2% poly(vinyl alcohol), 5% gelatin, 40% poloxamer-188, and 5% polyvinylpyrrolidone to a cylindrical frame, quenching with liquid nitrogen, and freeze-drying to prepare a fluorescent marker in the form of a solid pellet.

[0221] As a result of dispersion, similar to Figure 56, compositions were produced in which ICG-HSA-PMMA (P-188 1.0%) microparticles were dispersed in various other surfactants and biocompatible polymeric substances, and it was confirmed that the ICG-HSA-PMMA (P-188 1.0%) microparticles were uniformly dispersed in all composition solutions used.

[0222] Furthermore, according to the results shown in FIG. 57, it was confirmed that it is possible to produce a fluorescent marker in the form of a solid pellet using microparticles dispersed in a solution of 1% sodium alginate, 1% sodium hyaluronate, 2% sodium methylcellulose, 2% poly(vinyl alcohol), 5% gelatin, 40% poloxamer-188, and 5% polyvinylpyrrolidone.

[0223] Example 16: Preparation and analysis of near-infrared fluorescent markers in the form of microparticle-coated metal clips In this example, we aimed to demonstrate that it is possible to manufacture fluorescent markers using metal and nonmetallic materials by coating the surfaces of metal and nonmetallic materials with particles loaded with fluorescent dyes. For this purpose, IRDye 800CW-HSA-PMMA (without P-188) particles, which are particles manufactured using PMMA polymer, were dispersed in a latex solution, and then coated on the surface of a clip and dried to manufacture a metal clip coated with particles loaded with fluorescent dyes.

[0224] To prepare a coating solution with IRDye 800CW-HSA-PMMA (without P-188) microparticles dispersed, the microparticles were dispersed in a latex solution (Acrylonitrile-Butadinene Copolymer 36%, water 64%) to a concentration of 135.03 mg / mL. Then, 2 μL of the coating solution was evenly coated on both surfaces of the metal clip. After the solution was coated on the surface of the metal clip, it was dried at room temperature for 24 hours and then heat-treated at 100°C for 30 minutes to prepare a metal clip coated with IRDye 800CW-HSA-PMMA (without P-188) microparticles that can function as a fluorescent marker.

[0225] To evaluate the efficacy of IRDye 800CW-HSA-PMMA (without P-188) microparticle-coated metal clips as fluorescent markers, one side of a fluorescent clip coated with IRDye 800CW-HSA-PMMA (without P-188) microparticles was cut and fluorescent images were taken with the coated side facing up (λ ex = 780 / 20 nm, λ em =845 / 40 nm).

[0226] As shown in the photograph in Figure 58, it was confirmed that the particles were uniformly coated on the surface of the metal clip.

[0227] The region of interest (ROI) value analyzed from the fluorescent image of the metal clip coated with microparticles was 4.92 × 10 5 It was confirmed that it generated a stronger fluorescent signal than the ICG-HSA complex of the same concentration. From the results of Figures 58 and 59, it was confirmed that it is possible to produce fluorescent markers of various shapes by coating metal clips, etc. with particles loaded with near-infrared fluorescent dye.

[0228] From the above description, a person skilled in the art to which the present invention belongs will understand that the present invention can be implemented in other specific forms without changing its technical idea or essential features. In this regard, it should be understood that the above-described embodiments are illustrative in all respects and are not limiting. The scope of the present invention should be interpreted as including all modifications and variations derived from the meaning and scope of the claims below rather than the above detailed description, and the equivalent concepts thereof.

Claims

1. A polymeric microparticle for labeling a lesion, the polymeric microparticle being loaded with a near-infrared fluorescent dye, the near-infrared fluorescent dye forming a complex with human serum albumin or cyclodextrin.

2. The near infrared fluorescent dyes include indocyanine green, IRDye 800CW carboxylate (IRDye 800CW), Alexa Fluor 647, Alexa Fluor 660, Alexa Fluor 680, Alexa Fluor 700, Alexa Fluor 750, Alexa Fluor 780, Flamma 749, Flamma 774, Flamma 800, FSD Fluor TM 647, FSD Fluor TM 680, FSD Fluor TM 750, FSD Fluor TM 800, sulfocyanine 5 carboxylic acid (Cy5), sulfocyanine 5.5 carboxylic acid (Cy5.5), sulfocyanine 7 carboxylic acid (Cy7), or sulfocyanine 7.5 carboxylic acid (Cy7.5).

3. 2. The polymeric microparticle of claim 1, wherein the polymer is poly(lactide-co-glycolide) (PLGA), poly(DL-lactide-co-glycolide) (PDLGA), poly(glycolic acid) (PGA), poly(lactide) (PLA), poly(hydroxybutyrate), polycaprolactone (PCL), polydioxanone (PDO), poly(amino acid), polyanhydride, polyorthoester, or polyphosphazene.

4. The polymeric microparticle of claim 3 , comprising a block copolymer of the polymer and poly(ethylene oxide) (PEG).

5. The polymeric microparticle of claim 1 , wherein the polymer is poly(methyl methacrylate) (PMMA) or polycarbonate (PC).

6. The polymeric microparticles according to claim 1 , further comprising alginic acid or hyaluronic acid.

7. The polymeric microparticle of claim 1 , wherein the microparticle further comprises a surfactant.

8. The polymeric microparticle according to claim 7, wherein the surfactant is any one selected from the group consisting of polyvinyl alcohol, polyethylene glycol, Labrafil, Labrasol, medium chain triglyceride, lecithin, N-methyl pyrrolidone, polyvinyl pyrrolidone, hydropropyl methylcellulose, poloxamer, and Tween.

9. the microparticles comprising one or more cavities within the microparticles; The polymeric microparticle of claim 1 , wherein the complex is loaded into the cavity.

10. The polymeric microparticles of claim 1 , wherein the microparticles are for coating on the surface of a metal or non-metal material.

11. The polymeric microparticles according to claim 10, wherein the coating is performed by adhesives or rubber agents.

12. A method for producing polymeric microparticles for labeling lesions, comprising the steps of forming a complex between a near-infrared fluorescent dye and human serum albumin, or between a near-infrared fluorescent dye and cyclodextrin; and loading the complex into polymeric microparticles.

13. The method for producing polymeric microparticles for marking lesions described in claim 12, wherein a water-in-oil-in-water (W1 / O / W2) emulsion method is used as a method for loading the complex into the polymeric microparticles.

14. The method for producing polymeric microparticles for marking lesions according to claim 12, further comprising the step of mixing the near-infrared fluorescent dye with a hydrogel polymer to load the dye into the polymeric microparticles.

15. A composition for labeling a lesion, comprising the polymeric microparticles according to any one of claims 1 to 11.

16. 16. The composition for marking lesions according to claim 15, wherein the microparticles are mixed with methylcellulose, alginic acid, hyaluronic acid, polyvinyl alcohol, collagen, gelatin, Tween, Poloxamer, or polyvinylpyrrolidone.

17. The composition for marking lesions according to claim 16, wherein the composition is injectable via a syringe.

18. The composition for marking lesions according to claim 15, wherein the composition is in the form of a solid pellet.

19. 20. A method for labeling a lesion comprising the step of injecting the composition of claim 15 into an individual.

20. 16. Use of the composition of claim 15 for marking lesions.